Method for producing perovskite-type single crystal, and perovskite-type single crystal
Through multi-step firing treatment in atmospheric and reducing atmospheres, perovskite single crystals with high electromechanical coupling coefficient and high coercive field are prepared, which solves the problem of coercive field reduction of piezoelectric materials in the existing technology and is suitable for piezoelectric elements and ultrasonic motors.
Patent Information
- Application Number
- CN202510504539.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-02-28
- Filing Date
- 2025-04-22
- Publication Date
- 2025-10-24
AI Technical Summary
The existing technology solves the problems of high electromechanical coupling coefficient and reduced coercive field of piezoelectric materials.
The first perovskite single crystal is prepared by firing a raw material containing an acceptor in an atmospheric atmosphere, then firing it in a reducing atmosphere, and then further treating it in an atmospheric atmosphere to prepare a perovskite single crystal with a high coercive field value.
Perovskite single crystals with high electromechanical coupling coefficient and high coercive field are achieved, which are suitable for piezoelectric elements, ultrasonic motors, optical equipment, etc.
Smart Images

Figure CN120830147A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a method for manufacturing a perovskite single crystal and a perovskite single crystal. The present application also relates to a piezoelectric element, an ultrasonic motor, an optical device, a vibration device, a dust removing device, an imaging device, an ultrasonic probe, an ultrasonic diagnostic apparatus, an ultrasonic diagnostic system, and an electronic device using the single crystal. BACKGROUND
[0002] In recent years, high performance and miniaturization of piezoelectric devices have been promoted, and piezoelectric materials need to have higher piezoelectric properties than ever. A method of forming a single crystal in a piezoelectric material with crystal orientation alignment is known as a means to achieve enhancement of piezoelectric properties in a piezoelectric material. If a piezoelectric material is formed into a single crystal, a high electromechanical coupling coefficient is obtained, and as a result, piezoelectric properties are improved.
[0003] For example, Japanese Patent No. 3507821 discloses a solid phase method for single crystal formation of a piezoelectric material such as barium titanate, in which a single crystal used as a seed is joined to a matrix and heat treated to grow abnormal grains into an enlargement of only single crystal grains, and the abnormal grains are cut off to produce a single crystal.
[0004] Although the piezoelectric material obtained in the manufacturing method of Japanese Patent No. 3507821 has an enhanced electromechanical coupling coefficient by single crystal formation, the coercive field of the piezoelectric material is reduced, which indicates the strength of an external electric field that reaches zero polarization. If a piezoelectric material with a low coercive field is driven at a high voltage, the piezoelectric material disadvantageously loses piezoelectric properties. SUMMARY
[0005] Problems to be Solved by the Invention
[0006] Forming a single crystal by only the above-described conventional technique produces high piezoelectric characteristics, but disadvantageously leads to a problem of a coercive field reduction.
[0007] Solution to Problem
[0008] The present application has been made to solve such a problem, and an object of the present application is to provide a method for manufacturing a single crystal that exhibits a high electromechanical coupling coefficient and a high coercive field when used in a piezoelectric element. Furthermore, another object of the present application is to provide an ultrasonic motor, an optical device, a vibration device, a dust removing device, an imaging device, an ultrasonic probe, an ultrasonic diagnostic apparatus, an ultrasonic diagnostic system, and an electronic device using a piezoelectric element having a high electromechanical coupling coefficient and a high coercive field.
[0009] To solve the above problems, the present application provides a method for producing a perovskite single crystal, wherein a single crystal having a higher coercive field value than a first single crystal is produced by sequentially performing a step (1) of producing the first single crystal of perovskite type by firing a raw material containing an acceptor in an atmosphere, a step (2) of firing the first single crystal in a reducing atmosphere, and a step (3) of firing the single crystal produced in the step (2) in an atmosphere.
[0010] The present application also provides a perovskite single crystal containing an oxide having a perovskite structure and Mn, the oxide containing Ba, Ti, and Zr, wherein x as a molar ratio of Zr to the total of Ti and Zr satisfies 0.02 ≤ x ≤ 0.13, wherein the content of Mn of the single crystal is 0.04 mass parts or more and 0.36 mass parts or less with respect to 100 mass parts of the oxide in terms of metal, the single crystal optionally contains Bi, and the content of Bi is 0 mass parts or more and 0.20 mass parts or less with respect to 100 mass parts of the oxide in terms of metal, and the electromechanical coupling coefficient k 33 is 80% or more and the coercive field is 2.5 kV / cm or more.
[0011] The present application provides a piezoelectric element including a plurality of electrodes and a single crystal.
[0012] The present application provides an ultrasonic motor including: a vibration body provided with a piezoelectric element; and a moving body in contact with the vibration body.
[0013] The present application provides an optical apparatus including an ultrasonic motor in a driving section.
[0014] The present application provides a vibration device including a vibration body having a vibration plate provided with a piezoelectric element.
[0015] The present application provides a dust removing device including a vibration device in a vibration section.
[0016] The present application provides an imaging device including a dust removing device and an imaging element unit, wherein a vibration plate of the dust removing device is provided on a light-receiving surface side of the imaging element unit.
[0017] The present application provides an ultrasonic probe including a piezoelectric element, wherein the ultrasonic probe transmits and receives ultrasonic waves by the piezoelectric element.
[0018] The present application provides an ultrasonic diagnostic apparatus including an ultrasonic probe and an image output section.
[0019] The present application provides an ultrasonic diagnostic system including: an ultrasonic probe; a transmission section that transmits a signal output from the ultrasonic probe; and a reception section that receives a signal transmitted from the transmission section.
[0020] The present application provides an electronic device provided with a piezoelectric acoustic member including a piezoelectric element. BRIEF DESCRIPTION OF DRAWINGS
[0021] Other features of the present application will become apparent from the following description of exemplary embodiments with reference to the drawings.
[0022] Figure 1 is a schematic diagram for describing the first embodiment of the present application.
[0023] Figure 2 is a schematic diagram for describing the first embodiment of the present application.
[0024] Figure 3 is a schematic diagram for describing the first embodiment of the present application.
[0025] Figure 4 is a schematic diagram for describing the first embodiment of the present application.
[0026] Figure 5 is a schematic diagram for describing the first embodiment of the present application.
[0027] Figure 6 is a schematic diagram for describing the first embodiment of the present application.
[0028] Figure 7 is a schematic diagram for describing the first embodiment of the present application.
[0029] Figure 8 is a schematic diagram showing a configuration mode of a piezoelectric element of the present application.
[0030] Figure 9 is a schematic diagram showing a configuration mode of an ultrasonic motor of the present application.
[0031] Figure 10A is a schematic diagram showing a mode of an optical device of the present application.
[0032] Figure 10B is a schematic diagram showing another mode of an optical device of the present application.
[0033] Figure 11 is a schematic diagram showing a mode of an optical device of the present application.
[0034] Figure 12A is a schematic diagram showing a mode of a vibration device of the present application when used for a dust removing device.
[0035] Figure 12B is a schematic diagram showing another mode of a vibration device of the present application when used for a dust removing device.
[0036] Figure 13A Fig. 1 is a schematic diagram showing a configuration example of a piezoelectric element in a dust removing apparatus of the present application.
[0037] Figure 13B Fig. 2 is a schematic diagram showing another configuration example of a piezoelectric element in a dust removing apparatus of the present application.
[0038] Figure 13C Fig. 3 is a schematic diagram showing another configuration example of a piezoelectric element in a dust removing apparatus of the present application.
[0039] Figure 14A Fig. 4 is a schematic diagram showing an example of a vibration principle of a dust removing apparatus of the present application.
[0040] Figure 14B Fig. 5 is a schematic diagram showing another example of a vibration principle of a dust removing apparatus of the present application.
[0041] Figure 15 Fig. 6 is a schematic diagram showing a mode of an imaging apparatus of the present application.
[0042] Figure 16 Fig. 7 is a schematic diagram showing a mode of an imaging apparatus of the present application.
[0043] Figure 17 Fig. 8 is a schematic diagram showing a mode of an ultrasonic probe of the present application.
[0044] Figure 18 Fig. 9 is a schematic diagram showing a mode of an ultrasonic diagnostic apparatus of the present application.
[0045] Figure 19 Fig. 10 is a schematic diagram showing a mode of an ultrasonic diagnostic system of the present application.
[0046] Figure 20 Fig. 11 is a schematic diagram showing a mode of an ultrasonic diagnostic system of the present application.
[0047] Figure 21 Fig. 12 is a schematic diagram showing a mode of an electronic device of the present application.
[0048] Figure 22 Fig. 13 is a schematic diagram for describing an embodiment or mode of X-ray diffraction pole figure measurement of a single crystal of the present application.
[0049] Figure 23 Fig. 14 is a schematic diagram for describing an embodiment or mode of X-ray diffraction pole figure measurement of a single crystal of the present application.
[0050] Figure 24 Fig. 15 is a schematic diagram for describing an embodiment or mode of a PE hysteresis curve of a piezoelectric element having a single crystal of the present application.
[0051] Figure 25is a schematic diagram for describing an embodiment or a pattern of temperature dependence of a piezoelectric constant of a piezoelectric element having a single crystal of the present application.
[0052] Figure 26 is a schematic diagram for describing an embodiment or a pattern of temperature dependence of a relative dielectric constant of a piezoelectric element having a single crystal of the present application. DETAILED DESCRIPTION
[0053] Hereinafter, an embodiment for implementing the present application will be described.
[0054] The present application provides a method for manufacturing a perovskite-type single crystal having a high electromechanical coupling coefficient and a high coercive field, and a perovskite-type crystal prepared by the method.
[0055] The perovskite-type single crystal of the present application can be used for a piezoelectric element in various applications such as electronic devices including semiconductors, light emitting elements, optical elements, energy conversion elements, and sensors, and the like.
[0056] <First Embodiment>
[0057] The first embodiment relates to a method for manufacturing a perovskite-type single crystal.
[0058] The method for manufacturing a perovskite-type single crystal of the present application is characterized by preparing a single crystal having a higher coercive field value than a first single crystal by sequentially performing a step (1) of preparing the first single crystal of the perovskite type by firing a raw material containing an acceptor in an atmosphere, a step (2) of firing the first single crystal in a reducing atmosphere, and a step (3) of firing the single crystal prepared in the step (2) in an atmosphere.
[0059] The following describes basic matters for understanding the present application, and then describes each item.
[0060] [Explanation for Understanding the Invention - 1]
[0061] (Single Crystal)
[0062] The term "single crystal" refers to a crystal composed of a single grain such that a crystal axis that specifies an atomic arrangement direction is uniform inside the entire grain. However, the single crystal of the present application can include lattice defects such as dislocations, vacancies, voids, heterophases, amorphous, or organic matters inside the single crystal. In addition, the single crystal of the present application can include a domain structure, for example, generated by a difference in crystal system or a difference in spontaneous polarization direction due to an internal phase transition.
[0063] (Perovskite Type)
[0064] The term "perovskite type" refers to a perovskite structure that is ideally a cubic crystal structure, as described in Iwanami Rikagaku Jiten 5th edition (published by Iwanami Shoten, published on February 20, 1998). Perovskite-type oxides are generally represented by the chemical formula AB03. Although the molar ratio between the element at site A or site B and the element O is shown as 1:3, even oxides in which oxygen vacancies exist in a portion of the crystal and oxides in which the quantitative ratio of the elements deviates slightly can be said to be perovskite-type oxides as long as the oxides have a perovskite-type main phase. If the elements A, B, and O undergo slight coordinate shifts from the symmetric positions in the unit cell, the perovskite-type unit cell is deformed, resulting in a cubic, rhombohedral, or orthorhombic crystal system.
[0065] The perovskite-type single crystal of the present application contains a perovskite-type oxide, and the single crystal can take not only the cubic crystal system but also the cubic, rhombohedral, or orthorhombic crystal system by one or more elements constituting A and B. Whether the oxide is perovskite-type or what crystal system the oxide has can be determined by structural analysis, such as X-ray diffraction or electron beam diffraction. In this case, the sample can be pulverized before measurement, if necessary.
[0066] The method for producing the perovskite-type single crystal of the present application is specifically described below.
[0067] (Preparation of the first single crystal)
[0068] The first single crystal can be produced by any of a liquid phase method, a solid phase method, and a gas phase method, the liquid phase method including a Czochralski method, a Bridgman method, a floating zone melting method, and a flux method, the solid phase method including a solid phase reaction method and a sol-gel method, and the gas phase method including a sublimation method and a chemical vapor deposition, as long as the single crystal can be prepared in an atmospheric atmosphere.
[0069] The method for producing the single crystal of the present application includes a step (1) of firing a raw material containing an acceptor in an atmospheric atmosphere to produce a perovskite-type first single crystal.
[0070] (Acceptor)
[0071] The acceptor used in the method for producing the perovskite-type single crystal of the present application can be selected from the group consisting of elements having ions in which some of the ions of the elements in the perovskite-type single crystal are replaced after undergoing a reduction in valence.
[0072] Firing of a raw material containing an acceptor under an atmospheric atmosphere to produce a first single crystal of a perovskite type results in coercive field enhancement. When the valence of an ion of an element at a site of a perovskite single crystal is reduced below the original valence and is substituted by an acceptor, the charge balance of the crystal lattice is broken, and an oxygen vacancy is generated at an oxygen site to compensate for the balance, resulting in a dipole of the acceptor and the oxygen vacancy, thereby generating an internal electric field. The internal electric field hinders the polarization reversal caused by an external electric field, resulting in coercive field enhancement.
[0073] As a result of firing of a raw material containing an acceptor under an atmospheric atmosphere, the acceptor is less likely to enter a vacancy or the like as a substance other than the first single crystal, and substitution of the acceptor can be achieved at more sites of the perovskite type crystal.
[0074] For example, in a perovskite oxide configured by A 2+ B 4+ In a perovskite oxide of A
[0075] In a perovskite oxide of A 1+ B 5+ In a perovskite oxide of A
[0076] In a perovskite oxide of A 3+ B 3+ In a perovskite oxide of A
[0077] Here, the raw material used as the acceptor can be a metal, an oxide, a sulfide, or a nitride, as long as the raw material contains any of these elements, and the state can be solid or liquid.
[0078] The acceptor used in the method of manufacturing a single crystal of the present application can be Mn.
[0079] The valence of Mn ranges widely, from divalent to heptavalent, and can be used as an acceptor at A 2+ B 4+ In a perovskite oxide of A 1+ B 5+ In a perovskite oxide of A 3+ B3+ If Mn exists as an acceptor in the perovskite single crystal, oxygen vacancies are formed in the single crystal, and the Mn ion and the oxygen vacancy form a dipole to generate an internal electric field. The internal electric field hinders the polarization reversal caused by the external electric field, resulting in an increase in the coercive field.
[0080] In the case where conduction electrons exist due to the presence of donor elements such as impurities, the Mn ion successfully increases the insulation resistance by capturing the conduction electrons by undergoing a decrease in valence, and thus Mn can be used.
[0081] The valence of the trace amount of Mn added to the non-magnetic (diamagnetic) material can be evaluated by measuring the temperature dependence of the magnetic susceptibility. The magnetic susceptibility can be measured by a superconducting quantum interference device (SQUID), a vibrating sample magnetometer (VSM), or a magnetic balance. The magnetic susceptibility χ obtained in the measurement generally follows the Curie-Weiss law represented by the following formula 1:
[0082] χ = C / (T - θ) (C: Curie constant, θ: paramagnetic Curie temperature) (Formula 1).
[0083] The trace amount of Mn added to the non-magnetic material generally exhibits spin S = 5 / 2 at the 2+ valence, S = 2 at the 3+ valence, and S = 3 / 2 at the 4+ valence. Therefore, the Curie constant C converted per unit amount of Mn is a value corresponding to the spin S value at the different valence of Mn. Thus, the average valence of Mn in the sample can be evaluated by deriving the Curie constant C from the temperature dependence of the magnetic susceptibility χ.
[0084] (Sequentially fired under a reducing atmosphere and under an atmospheric atmosphere)
[0085] The method for manufacturing a perovskite single crystal of the present application is characterized by sequentially including a step (2) including firing a first single crystal prepared by the above method under a reducing atmosphere and a step (3) including firing the single crystal prepared in the step (2) under an atmospheric atmosphere. By this method, a perovskite single crystal having a higher coercive field value than the first single crystal is prepared.
[0086] The first single crystal of the perovskite type prepared by firing a raw material containing an acceptor under an atmospheric atmosphere is inferred to contain a substitution acceptor ion that maintains the same valence as the original element and an acceptor ion that remains in a vacancy portion in a non-perovskite state. When this first single crystal is fired under a reducing atmosphere, further oxygen vacancies are generated to be added to the oxygen vacancies originally present in the first single crystal, and it is inferred that the residual acceptor ion as described above is introduced into a site in the single crystal.
[0087] Accordingly, acceptor ions and oxygen vacancies form more dipoles, resulting in a stronger internal electric field. The internal electric field hinders the polarization reversal caused by the external electric field, resulting in a greatly enhanced coercive field.
[0088] By firing under a reducing atmosphere, the maximum value of the relative dielectric constant ε 33 of the single crystal decreases, and the change amplitude (%) of the piezoelectric constant d 33 decreases.
[0089] In general, when the temperature of a piezoelectric material changes toward the phase transition temperature, rearrangement or loss of polarization occurs, and the polarization change caused by the external electric field, i.e., the relative dielectric constant, increases. This change is significant for single crystals. However, if the acceptor increases the internal electric field, the polarization change caused by the external electric field decreases, resulting in a decrease in the relative dielectric constant. The piezoelectric constant d 33 is a function of the relative dielectric constant, as shown in the following equation (2), so the change amplitude upon temperature change decreases for the same reason:
[0090]
[0091] where d denotes the piezoelectric constant, k denotes the electromechanical coupling coefficient, ε T denotes the dielectric constant as the product of the relative dielectric constant and the vacuum dielectric constant, and Y denotes the Young's modulus.
[0092] (firing under a reducing atmosphere)
[0093] Next, the step (2) of firing the first single crystal under a reducing atmosphere will be specifically described with reference to Figure 1 and Figure 2 .
[0094] Figure 1 is a schematic view showing the configuration of a reducing atmosphere firing furnace 2 for firing the first single crystal 1 under a reducing atmosphere. In the reducing atmosphere firing furnace 2, the first single crystal 1 is placed in a high-temperature electric furnace 3 configured to be able to purge the atmosphere inside the high-temperature electric furnace 3 with a gas such as a non-active gas discharged from a gas cylinder 4. In order to control the oxygen partial pressure in the high-temperature electric furnace, an oxygen partial pressure controller 5 is provided. For example, SiOC-200CB (manufactured by STLab CO., LTD.) can be used as the oxygen partial pressure controller. Figure 1
[0095] Figure 2 An exemplary configuration diagram for setting the first single crystal 1 in the reducing atmosphere firing furnace 2 is shown.
[0096] The first single crystal 1 placed on the setter 6 can be set in the high-temperature electric furnace 3 in the reducing atmosphere firing furnace 2 in this state. Figure 1 In the reducing atmosphere firing furnace 2, the first single crystal 1 placed on the setter 6 can be set in the high-temperature electric furnace 3 in this state.
[0097] A material that does not react at all with the first single crystal 1 is suitable for the setter 6; for example, alumina, zirconia, alumina coated with zirconia on the surface, stabilized zirconia, silicon carbide, or silicon nitride can be used. If it is difficult to determine whether the material does not react at all, the material can be actually tested to select a material with the least firing trace.
[0098] (reducing atmosphere)
[0099] The reducing atmosphere can be a space filled with an oxygen-free gas or vacuum, and one or more gases can be selected from the group consisting of hydrogen, helium, carbon monoxide, hydrocarbon, argon, nitrogen, ammonia, and the like, and the gas can be an argon-containing gas. Among the inactive gases, argon does not react at all with the first single crystal, and thus more oxygen vacancies can be generated, thereby generating a stronger coercive field. A reducing atmosphere containing 90 mol% or more of argon can be used because the effect of generating more oxygen vacancies is significant.
[0100] In addition, the oxygen partial pressure P(O2) of the reducing atmosphere can be 1 x 10 -10 Pa or less. The oxygen partial pressure of 1 x 10 -10 Pa or less allows more oxygen vacancies to be generated, thereby generating a stronger coercive field.
[0101] The firing temperature in step (2) in which the single crystal prepared in step (1) is fired in a reducing atmosphere can be equal to or lower than the firing temperature at which the first single crystal is prepared in step (1), and can be 1280°C or higher. Firing at a temperature lower than that at which the first single crystal is prepared is less likely to cause the generation of a heterophase, which is a crystal different from the perovskite, and the single crystal structure is likely to be maintained, thus preparing a single crystal having a high electromechanical coupling coefficient.
[0102] (firing in an atmospheric atmosphere)
[0103] Next, step (3) in which the single crystal prepared in step (2) is fired in an atmospheric atmosphere will be described. Step (2) includes firing the first single crystal in a reducing atmosphere.
[0104] Figure 3 is a schematic diagram for describing the first embodiment of the present application.
[0105] Step (3) after the first single crystal 1 is fired in a reducing atmosphere according to the present application includes firing the resultant in an atmospheric atmosphere. As shown in Figure 3 Step (3) can be performed by placing the first single crystal 1 fired in a reducing atmosphere and placed on the setter 6 in a crucible 7 and placing the crucible 7 in an electric furnace to perform firing. The firing can be performed with a lid (not shown) to prevent contamination by surrounding impurities.
[0106] A general electric furnace can be used for firing in an atmospheric atmosphere; for example, a super electric furnace (SSFT-1520 manufactured by YAMADA DENKI CO., LTD.) can be used.
[0107] The single crystal of the present application prepared by firing the first single crystal 1 in a reducing atmosphere and then firing the resultant in an atmospheric atmosphere exhibits a high electromechanical coupling coefficient when used for a piezoelectric element because the heterophase generated upon firing in a reducing atmosphere has been removed.
[0108] The firing temperature upon firing in an atmospheric atmosphere in step (3) can be equal to or lower than the firing temperature upon firing in a reducing atmosphere in step (2) and can be 1000°C or lower. Firing in an atmospheric atmosphere at a temperature equal to or lower than the temperature upon firing in a reducing atmosphere allows better retention of the oxygen vacancies introduced upon firing in a reducing atmosphere, thereby generating a higher coercive field.
[0109] (Method for producing first single crystal)
[0110] Next, an example of a specific production method for producing the first single crystal 1 will be described.
[0111] The production of the first single crystal 1 in the present application can be a solid phase growth method.
[0112] Since the formation of a melt and cooling in a liquid phase method is not involved, the first single crystal 1 can be produced by a solid phase growth method, and thus even in the case where an inconsistent melt composition (inconsistent composition) is generated by the addition of an acceptor, the first single crystal 1 having almost the same composition as the raw material containing the acceptor can be produced.
[0113] Embodiments of the production of the first single crystal by a solid phase growth method are described below.
[0114] Figure 4 is a schematic view showing an embodiment of the integrated product of the seed single crystal 11 and the base 12 in the present application. In Figure 4 In the present embodiment, the seed single crystal 11 is disposed on the base 12 to form an integrated product in which the surface of the base 12 and the surface in the seed single crystal 11 are in contact with each other.
[0115] The production method of the first single crystal of the present application is a production method in which the base 12 is caused to form a single crystal by firing the base 12 in the integrated product, for example, as shown in Figure 4 .
[0116] (Explanation of base)
[0117] Figure 4The base 12 in the above embodiment can be a molded body or a sintered body. The raw material for the base 12 is a solid powder of an oxide, a carbonate, a nitrate, an oxalate, or the like of a constituent element of the single crystal of the present application including the acceptor, or a mixed powder of these solid powders.
[0118] Examples of the elements of the raw material constituting the base 12 include Li, Na, Mg, Al, Si, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ge, Sr, Y, Zr, Nb, Mo, In, Sn, Sb, Ba, Hf, Ta, Pb, Bi, La, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, and Yb.
[0119] Here, since the environmental load is low, it is more preferable that the content of lead (Pb) in the raw material be less than 1000 ppm.
[0120] In the case where the elements Ba, Ti, and Zr are used and the element Mn is used as the acceptor, for example, examples of the applicable Ba raw material include barium oxide, barium carbonate, barium oxalate, barium acetate, barium nitrate, barium titanate, and barium zirconate. For these Ba compounds, a commercially available high-purity type compound (for example, a purity of 99.99% or more) can be used.
[0121] Examples of the applicable Ti raw material include titanium oxide, barium titanate, and barium zirconate titanate. In the case where an alkaline earth metal such as barium is contained in this Ti compound, a commercially available high-purity type compound (for example, a purity of 99.99% or more) can be used.
[0122] The content of Nb can be the same as the content of unavoidable component Nb in a commercially available Ti raw material, and the content of Hf can be the same as the content of unavoidable component Hf in a commercially available Zr raw material.
[0123] Examples of the applicable Zr raw material include zirconium oxide, barium zirconate, and barium zirconate titanate. In the case where an alkaline earth metal such as barium is contained in this Zr compound, a commercially available high-purity type compound (for example, a purity of 99.99% or more) can be used.
[0124] Examples of the applicable Mn raw material include manganese carbonate, manganese oxide, manganese dioxide, manganese acetate, and trimanganese tetraoxide.
[0125] The raw material of the base 12 can contain Bi. If the content of Bi in terms of metal is 0.20 parts by mass or less with respect to 100 parts by mass of the perovskite-type metal oxide that is the main component of the base 12, trivalent Bi ions can occupy the sites A. This causes the Mn ions of the sites B to have a valence lower than 4+, facilitates charge balance, and promotes the Mn ions as acceptor ions.
[0126] In the case where Bi is used as the raw material of the substrate 12, examples of the Bi raw material that can be used include bismuth oxide and bismuth chloride.
[0127] A compound that promotes single crystal formation by a solid phase growth method can be added to the raw material of the substrate 12. Examples of the promoter element include lithium (Li), silicon (Si), and aluminum (Al), and the Li content can be 0.05 parts by mass or more and 0.20 parts by mass or less with respect to 100 parts by mass of the perovskite-type metal oxide that is the main component of the substrate 12, in terms of metal.
[0128] In the case where Li is used as the raw material of the substrate 12, examples of the Li raw material that can be used include lithium carbonate, lithium tetraborate, and lithium acetate.
[0129] Any raw material can be used to adjust a, which represents the ratio between the abundance of Ba ions at site A and the molar amount of Ti and Zr at site B in the single crystal according to the present application, without particular limitation. Ba compounds, Ti compounds, and Zr compounds have the same effect.
[0130] (Pelletization of the raw material for producing the substrate)
[0131] The raw material of the substrate 12 used in the method for producing the single crystal of the present application can be pelletized, and the pelletization is not limited to any particular method. Examples of the binder that can be used in the pelletization include PVA (polyvinyl alcohol), PVB (polyvinyl butyral), and an acrylic resin.
[0132] (Molding of the raw material for producing the substrate)
[0133] The molding of the substrate 12 used in the method for producing the single crystal of the present application is a molding made by hardening the raw material into a desired shape, and the production is not limited to a particular method. The molding is a solid made from a powder, a granular powder (containing a binder), or a slurry of the raw material.
[0134] For example, uniaxial pressing, cold isostatic pressing, warm isostatic pressing, casting molding, or extrusion molding can be used as a means for producing the molding. The raw material in the form of a slurry can be shaped into a sheet by a doctor blade method, then dried, and these sheets can be stacked to form the intended shape.
[0135] (Sintering)
[0136] In the case where the sintered body is used as the substrate 12, the molding can be sintered and the sintering means is not limited, examples of the sintering method include sintering with an electric furnace, sintering with a gas furnace, a hot-pressing method, an electric heating method, a microwave sintering method, a millimeter wave sintering method, HIP (hot isostatic pressing), and a flash sintering method.
[0137] (Seed single crystal)
[0138] The seed single crystal 11 for preparing the first single crystal can be a bulk or a thin film. The seed single crystal 11 can be prepared by selecting from the group consisting of commercially available oxide single crystals, semiconductor single crystals, fluoride alkali halide single crystals, metal single crystals, alloy single crystals, and the like, but a perovskite single crystal is preferable because the tendency of stress generation due to lattice constant mismatch and thermal expansion difference of the base 12 is low.
[0139] Examples of the perovskite single crystal used as the seed single crystal 11 include BaTiO3, BaZrO3, SrTiO3, CaTiO3, Pb(Mg 1 / 3 Nb 2 / 3 )O3, KTaO3, KNbO3, SrRuO3, LiNbO3, LaNiO3, AgNbO3, CdTiO3, and solid solutions of any of these perovskite single crystals.
[0140] The first single crystal prepared by the above method can be used as the seed single crystal 11 used when preparing the first single crystal.
[0141] (polish)
[0142] The base 12 and the seed single crystal 11 obtained by sintering as described above are polished, and the polished surfaces of the base 12 and the seed single crystal 11 are arranged in contact to form a unification; as a result, a larger contact area can be achieved.
[0143] The polishing method includes mechanical polishing, chemical polishing, and CMP polishing, and the polishing can be performed in combination of these polishing methods.
[0144] (saggar, setter, beads, weight)
[0145] Figure 5 、 Figure 6 and Figure 7 are exemplary schematic diagrams showing the arrangement for preparing the first single crystal. In Figure 5 , a weight 14 is placed on top of the unification of the base 12 and the seed single crystal 11, and the unification is arranged above a setter 16 by beads 15. Figure 6 showing a case where they are placed in a saggar 17, Figure 7 showing Figure 6 the saggar 17 in is covered with a lid 18, and the saggar 17 covered with the lid 18 is placed in an electric furnace for firing.
[0146] The substrate 12 and the seed single crystal 11 can be arranged vertically to contact. Since the substrate 12 and the seed single crystal 11 can be easily contacted, the weight 14 can be placed on the substrate 12 and the seed single crystal 11. Even if a force acts in a direction in which the substrate 12 and the seed single crystal 11 are separated from each other due to deformation or the like in heat treatment, the weight 14 exerts a force acting in a direction in which separation is prevented, thereby facilitating contact.
[0147] The substrate 12 and the seed single crystal 11 can be subjected to heat treatment on a setter 16 that does not react with the substrate 12 and the seed single crystal 11 at all. As a material for the setter 16, for example, alumina, zirconia, alumina coated with zirconia on the surface, stabilized zirconia, silicon carbide, or silicon nitride can be used. The substrate 12 and the seed single crystal 11 can be placed on a bead 15 of stabilized zirconia or the like, a powder obtained by sintering the substrate 12 at a high temperature and breaking the resultant, or a platinum sheet that has been placed on the setter 16. If it is difficult to determine whether or not a material does not react at all, the material can be actually tested to select a material having the least sintering trace.
[0148] (Liquid phase of substrate)
[0149] The substrate 12 for producing the first single crystal 1 has a liquid phase appearance temperature and a liquid phase disappearance temperature. The term "liquid phase" herein refers to a state in which at least a part of the substrate 12 is in a liquid phase, and a state in which a solid phase and a liquid phase coexist is also regarded as a liquid phase. For example, the state and the temperature can be confirmed in such a manner that a sample is placed on a heating stage of a microscope (manufactured by Linkam Scientific Instruments Ltd.) and the temperature is increased, and the surface of the substrate 12 is observed with the microscope. Specifically, a temperature at which at least a part of the grain boundaries of the substrate 12 becomes unobservable during temperature increase is the liquid phase appearance temperature, which indicates transition to a liquid phase, and a temperature at which the grain boundaries of the substrate 12 are at least partially generated by further temperature increase is the liquid phase disappearance temperature.
[0150] Since the liquid phase becomes an amorphous state by rapid cooling, as another way, the temperature of transition to a liquid phase can be confirmed by structural analysis of whether or not an amorphous region is present in the substrate 12 that has been subjected to heating to a temperature close to a liquid phase temperature and then directly placed in tap water or the like at room temperature and subjected to rapid cooling.
[0151] The liquid phase appearance temperature in the present application varies due to the influence of impurity contamination at the time of production, unevenness of pressure at the time of molding, voids, or the like. Therefore, a range of the lowest temperature ± 50°C in which a liquid phase can be confirmed by the above means is defined as the liquid phase appearance temperature. A range of the highest temperature ± 50°C in which a liquid phase can be confirmed by the above means is defined as the liquid phase disappearance temperature.
[0152] When the interface between the seed single crystal 11 and the base 12 turns into a liquid phase, the interface of the single crystal region in the seed single crystal 11 gradually propagates to the base 12. At this time, due to the difference in surface energy, it is inferred that the grains of the base 12 are introduced into the single crystal. Therefore, the overlarge grains of the base 12 result in a smaller difference in surface energy, and thus the base 12 is less likely to be introduced into the single crystal.
[0153] Therefore, in the case where the base 12 is prepared as a sintered body, the base 12 is sintered at a temperature that does not result in the formation of overlarge grains. As a means of preventing the increase in grain size, a method of sintering under a reducing atmosphere of nitrogen gas, argon gas, or the like as a sintering reducing atmosphere can be used.
[0154] (Firing method)
[0155] In the first temperature increase, the second temperature increase, and the firing described later, the firing of the integrated body of the base 12 and the seed single crystal 11 is not limited to a particular method, but is performed in an atmosphere, but the firing with an electric furnace can fire many integrated bodies at a time, thereby achieving a reduction in production cost.
[0156] [First temperature increase]
[0157] The method for preparing the first single crystal 1 includes a first temperature increase of increasing the temperature of the integrated body from room temperature to the liquid phase appearance temperature of the base.
[0158] In the first temperature increase of increasing the temperature to the liquid phase appearance temperature, the grains in the base grow almost uniformly. As described above, if the grains of the base 12 grow too large, the base 12 is less likely to be introduced into the first single crystal, and thus the first temperature increase can be set to be performed for a short time so as not to grow too large.
[0159] [Second temperature increase]
[0160] The method for preparing the first single crystal 1 includes a second temperature increase of increasing the temperature of the integrated body from the liquid phase appearance temperature of the base 12 to the liquid phase disappearance temperature.
[0161] In the second temperature increase, the interface between the seed single crystal 11 and the base 12 turns into a liquid phase, and the single crystal interface propagates to the base 12. However, if the temperature has a spatial variation, for example, due to the difference in grain orientation of the base 12 in contact with the seed single crystal 11, the interface of the grains having different orientations in the base 12 also propagates at the same time, and in some cases, the single crystal as a single grain cannot be successfully prepared.
[0162] Therefore, by adopting a smaller temperature increase rate from the liquid phase appearance temperature to the liquid phase disappearance temperature in the second temperature increase than the temperature increase rate from room temperature to the liquid phase appearance temperature in the first temperature increase, the single crystal region composed of single grains is allowed to propagate from the seed single crystal 11.
[0163] After the temperature is increased, by maintaining the temperature at the liquid phase disappearance temperature, the size of the single crystal region propagated from the seed single crystal 11 can be further increased.
[0164] [Preparation of the first single crystal]
[0165] The method for preparing the first single crystal 1 includes preparing the first single crystal 1 from the base 12 after firing.
[0166] After the second heating, the location of the single crystal region in the matrix can be confirmed by microscopic examination of the presence of grain boundaries. Regions without any grain boundaries are single crystal regions consisting of single grains. Alternatively, single crystal regions can be confirmed by structural analysis using X-ray diffraction or electron beam diffraction.
[0167] The first single crystal can be prepared by removing the polycrystalline portion and the seed single crystal 11 portion other than the single crystal region with a wire saw or a dicing saw, or by any of water jet cutting, discharge machining, laser machining, grinding, etc., to separate the single crystal region.
[0168] The first single crystal is a single crystal containing a perovskite-type oxide and Mn, wherein the oxide contains Ba, Ti and Zr, wherein x is the molar ratio of Zr to the sum of Ti and Zr, and satisfies 0.02≤x≤0.13, and the Mn content is greater than or equal to 0.04 parts by mass and less than or equal to 0.36 parts by mass relative to 100 parts by mass of the oxide, calculated as metal.
[0169] Including Zr and Mn in amounts satisfying these ranges results in a low incidence of abnormal grain growth in portions other than the interface between seed single crystal 11 and substrate 12. If abnormal grain growth occurs in portions other than the interface between seed single crystal 11 and substrate 12, that portion can hinder the growth of the single crystal propagating from the interface between seed single crystal 11 and substrate 12. The first single crystal may contain an oxide containing Ba, Ti, and Zr, where x is the molar ratio of Zr to the sum of Ti and Zr, and satisfies 0.02 ≤ x ≤ 0.13, and the Mn content is 0.04 parts by mass or more and 0.36 parts by mass or less relative to 100 parts by mass of the oxide calculated as metal, the Bi content is greater than 0 parts by mass and 0.20 parts by mass or less relative to 100 parts by mass of the oxide calculated as metal, and the Li content is 0.05 parts by mass or more and 0.20 parts by mass or less relative to 100 parts by mass of the oxide calculated as metal.
[0170] The perovskite single crystal of the present invention is prepared by sequentially performing step (2) comprising firing a first single crystal prepared by a solid phase growth method under a reducing atmosphere and step (3) comprising firing the single crystal prepared in step (2) under an atmospheric atmosphere, and has a higher coercive field value than the first single crystal.
[0171] <Second Embodiment>
[0172] The second embodiment relates to a perovskite single crystal of the present application.
[0173] The perovskite single crystal of the present application is a single crystal containing an oxide having a perovskite structure containing Ba, Ti, and Zr, and Mn, wherein x is the molar ratio of Zr to the total of Ti and Zr, satisfies 0.02≤x≤0.13, wherein the Mn content of the single crystal is 0.04 mass parts or more and 0.36 mass parts or less with respect to 100 mass parts of the oxide in terms of metal, the single crystal optionally contains Bi, and the Bi content is 0 mass parts or more and 0.20 mass parts or less with respect to 100 mass parts of the oxide in terms of metal, the electromechanical coupling coefficient k 33 is 80% or more and the coercive field is 2.5 kV / cm or more.
[0174] Here, the Mn content "in terms of metal" means the amount given below: the metal contents of Ba, Ti, Zr, and Mn of the single crystal are measured by X-ray fluorescence analysis (XRF), ICP emission spectrometry, atomic absorption spectrometry, or the like; the metal contents are converted into the mass of the oxide of the elements constituting the oxide represented by the following general formula (3); the ratio of the mass of Mn to the total mass of 100 is determined, and the resulting value is the Mn content.
[0175] Ba a (Ti 1-x ,Zr x )O3(3)
[0176] The single crystal of the present application can contain a Pb component of less than 1000 ppm. Since it does not contain lead, the single crystal of the present application can achieve a low environmental load.
[0177] The general formula (3) of the oxide means that the element located at site A is Ba, and the element located at site B is Ti or Zr. However, some Ba ions can be located at site B. Likewise, some Ti and Zr ions can be located at site A.
[0178] Although the molar ratio of the element at site B to the element O in general formula (3) is 1:3, the ratio of the element contents can deviate, for example, due to oxygen vacancies generated by substitution with Mn at site B.
[0179] The single crystal of the present application can contain 90 mol% or more of the perovskite oxide represented by general formula (3) as a main component. A further range is 95 mol% or more.
[0180] In General Formula (3), x represents the mole ratio of Zr at site B, and is in the range of 0.02 ≤ x ≤ 0.13. If x is greater than 0.13, the Curie temperature becomes too low, resulting in insufficient high-temperature durability. If x is less than 0.02, the piezoelectric constant at room temperature is low.
[0181] The Curie temperature (Tc) is the temperature at which the ferroelectricity of a material disappears. Generally, when the temperature is raised to exceed Tc, the piezoelectric properties of a piezoelectric material disappear. Methods of measuring Tc include a method of directly determining the temperature at which the ferroelectricity disappears while measuring the temperature change, and a method of measuring the relative dielectric constant while measuring the change in temperature with respect to a small alternating electric field, and determining Tc from the temperature at which the local maximum of the relative dielectric constant is present.
[0182] The measurement of the composition of the single crystal of the present application is not limited to a specific means. Examples of these means include X-ray fluorescence analysis, ICP emission spectrometry, and atomic absorption spectrometry. The mass ratio and the composition ratio of the elements contained in the single crystal can be calculated using any of these means.
[0183] The single crystal of the present application has enhanced insulation resistance when containing Mn in an amount satisfying the above range. In the case where a piezoelectric element including the single crystal and a pair of electrodes is used as a device, when the device is driven by applying a voltage, the high insulation resistance resulting from the Mn content being 0.04 mass parts or more and 0.36 mass parts or less does not cause unnecessary current flow, and thus low power consumption is achieved.
[0184] On the other hand, if the Mn content is greater than 0.36 mass parts, the abundance of a heterogeneous phase different from the perovskite-type single crystal is high, and the insulation properties of the single crystal are low. For example, the dielectric loss tangent of the single crystal at a frequency of 1 kHz exceeds 0.01, and the resistivity decreases to less than 1 GΩcm. The dielectric loss tangent can be measured using an impedance analyzer. If the dielectric loss tangent is 0.01 or less, stable operation can be successfully achieved even when a high voltage is applied to a piezoelectric element using the single crystal.
[0185] If the resistivity of the single crystal is at least 1 GΩcm, the single crystal can be polarized, and can be driven as a piezoelectric element. Furthermore, the resistivity is 50 GΩcm or more.
[0186] The single crystal has an electromechanical coupling coefficient k of 80% or more at 25°C 33 In the case where a piezoelectric element including the single crystal and a pair of electrodes is used as a vibration device, efficient conversion from electric energy to mechanical energy is achieved, and low power consumption is achieved.
[0187] The single crystal has a coercive field of 2.5 kV / cm or more, and when a piezoelectric element including the single crystal and a pair of electrodes is used as a vibration device, the piezoelectric element is allowed to be driven without loss of piezoelectric properties even in products to be driven at high voltage such as ultrasonic motors and piezoelectric acoustic parts.
[0188] The single crystal can have a coercive field of 4 kV / cm or more when used for a vibration device. This range allows more kinds of products to be driven without loss of piezoelectric properties.
[0189] The piezoelectric constant d 33 of the single crystal of the present application can have a variation amplitude (%) of 65% or less, which is represented by the following expression (4):
[0190] 100 x Δd 33@0 ℃ 至70 ℃ / d 33@0 ℃ (4).
[0191] The relative dielectric constant ε 33 of the single crystal of the present application can have a maximum value in a range of 0°C or more and 70°C or less of 6500 or less.
[0192] The relative dielectric constant ε 33 of the single crystal of the present application can have a maximum value in a range of 0°C or more and 60°C or less of 4200 or less.
[0193] As described above, a piezoelectric material formed as a single crystal generally undergoes very large changes in the relative dielectric constant ε 33 and the piezoelectric constant d 33 around the phase transition temperature. Therefore, when a single crystal having piezoelectric properties is used for a device in a product such as a household appliance, for example, an ultrasonic motor in a camera, an increase in the relative dielectric constant of the piezoelectric material or a change in the piezoelectric constant (for example, a change of more than 65%) occurs in the working temperature range of the product (for example, 0°C or more and 70°C or less). If the relative dielectric constant increases, the capacitive component of the drive circuit increases, and the current flowing in the circuit increases. This disadvantageously leads to greater power consumption at the time of driving. In addition, the change in the piezoelectric constant disadvantageously changes the output characteristics (mainly the vibration amplitude) of the device, resulting in poor controllability.
[0194] Therefore, when a single crystal is used for a product such as a household appliance, it is required that the single crystal undergoes a small change in the piezoelectric constant in the working temperature range of the product. The variation amplitude of the piezoelectric constant with respect to temperature is 65% or less, and stable product performance is obtained in the working temperature range.
[0195] The relative dielectric constant ε 33In a case where the maximum value in the range of 0°C or higher and 70°C or lower is 6500 or lower, lower power consumption is achieved when used in the operating temperature range.
[0196] In a case where the maximum value in the range of 0°C or higher and 70°C or lower is 6500 or lower, lower power consumption is achieved when used in the operating temperature range. 33 In a case where the maximum value in the range of 0°C or higher and 60°C or lower is 4200 or lower, which is a more frequently used temperature range, lower power consumption is achieved when used in the operating temperature range.
[0197] <APPLICATION EXAMPLE>
[0198] An application example of the present application is described below.
[0199] (Piezoelectric Element)
[0200] The piezoelectric element of the present application includes a plurality of electrodes and the single crystal described above.
[0201] Figure 8 is a schematic diagram showing an embodiment of the configuration of the piezoelectric element of the present application. The piezoelectric element according to the present application is a piezoelectric element including at least a first electrode 21, a single crystal portion 22, and a second electrode 23, characterized in that the single crystal portion 22 is the single crystal of the present application.
[0202] The electromechanical coupling coefficient, the coercive field, the piezoelectric constant, and the relative dielectric constant of the single crystal according to the present application can be evaluated by introducing the single crystal into a piezoelectric element including at least a first electrode 21 and a second electrode 23. Each of the first electrode 21 and the second electrode 23 includes an electrically conductive layer having a thickness of about 5 nm to 10 μm. The material is not limited to a specific material, and can be a material generally used for piezoelectric elements. Examples of the material can include metals such as Ti, Pt, Ta, Ir, Sr, In, Sn, Au, Al, Fe, Cr, Ni, Pd, Ag, and Cu, and alloys and compounds of these metals.
[0203] Each of the first electrode 21 and the second electrode 23 can be an electrode composed of one of these materials, or an electrode obtained by laminating two or more of these materials. The material of the first electrode 21 and the material of the second electrode 23 can be different from each other.
[0204] The production of the first electrode 21 and the second electrode 23 is not limited to a specific method, and the first electrode 21 and the second electrode 23 can be formed by baking with a metal paste, or by sputtering, a vapor deposition method, or the like. Each of the first electrode 21 and the second electrode 23 can be formed by patterning to produce a desired shape for use.
[0205] (Polarization Treatment)
[0206] The polarization axis in the piezoelectric element can be aligned in a specific direction. The alignment of the polarization axis in a certain direction gives the piezoelectric element a higher electromechanical coupling coefficient.
[0207] The polarization of the piezoelectric element is not limited to a specific method. The polarization treatment can be performed in the atmosphere or in silicone oil. The polarization temperature can be the temperature at which the single crystal undergoes a phase transition. For example, the temperature can be 60°C to 150°C, but the optimum conditions depend to some extent on the composition of the single crystal constituting the element. The electric field strength for the polarization treatment can be 8 kV / cm to 20 kV / cm, and the application of the electric field is completed after the ambient temperature is lowered to a temperature at which the single crystal reaches the same crystal structure as at room temperature, since a good electromechanical coupling coefficient is obtained.
[0208] The range of the piezoelectric element according to the present application includes a laminated piezoelectric element produced by laminating a number of layers, each layer being a single crystal of the present application, or produced by stacking a number of piezoelectric elements into a rod, to utilize displacement in the thickness direction.
[0209] (Ultrasonic motor)
[0210] The ultrasonic motor of the present application includes a vibrating portion provided with the above-described piezoelectric element, and a moving portion in contact with the vibrating portion. With this configuration, it is possible to provide an ultrasonic motor having a driving efficiency equivalent to or higher than that in the case of using a lead-containing piezoelectric element. Figure 9 is a schematic diagram showing a configuration mode of the ultrasonic motor of the present application. Figure 9An ultrasonic motor in which the piezoelectric element of the present application includes a single plate is shown in FIG. 8. The ultrasonic motor includes a vibrator 201, a rotor 202 in pressure contact with a sliding surface of the vibrator 201 by pressure force applied by a pressure spring not shown, and an output shaft 203 integrally provided on the rotor 202. The vibrator 201 is composed of an elastic ring 2011 made of metal, the piezoelectric element 2012 of the present application, and an organic adhesive 2013 (epoxy resin, cyanoacrylate, etc.) that adheres the piezoelectric element 2012 to the elastic ring 2011. The piezoelectric element 2012 of the present application is composed of a single crystal sandwiched between a first electrode 21 and a second electrode 33 not shown. When an alternating voltage of two phases that differ by π / 2 times an odd number is applied to the piezoelectric element of the present application, a bending traveling wave is generated in the vibrator 201, and each point on the sliding surface of the vibrator 201 moves elliptically. If the rotor 202 is in pressure contact with the sliding surface of the vibrator 201, the rotor 202 receives a frictional force from the vibrator 201 and rotates in a direction opposite to the direction of the bending traveling wave. A driven body not shown is engaged to the output shaft 203 and is driven by the rotational force of the rotor 202. When a voltage is applied to the single crystal, the single crystal undergoes expansion and contraction vibration due to the piezoelectric transverse effect. The conversion efficiency from electric energy to mechanical energy depends on the size of the electromechanical coupling coefficient. If an elastic body such as metal is adhered to the piezoelectric element via an adhesive or the like, the elastic body is bent via the adhesive by the expansion and contraction vibration of the single crystal. The ultrasonic motor of the type described here utilizes this principle.
[0211] (Optical apparatus)
[0212] The optical apparatus of the present application includes the above-described ultrasonic motor in a driving section. With this configuration, an optical apparatus can be provided that has an operation speed and an operation efficiency comparable to or higher than those in the case of using a piezoelectric element containing lead.
[0213] Figure 10A and Figure 10B is a main sectional view of a replaceable lens barrel of a single-lens reflex camera that is an example of an embodiment of the optical apparatus of the present application. Figure 11 is an exploded perspective view of a replaceable lens barrel of a single-lens reflex camera that is an example of an embodiment of the optical apparatus of the present application. A fixed barrel 712, a straight guide barrel 713, and a front lens barrel 714 are fixed to a mount 711 for attaching and detaching a camera. These are fixed components of the replaceable lens barrel.
[0214] In the straight guide barrel 713, a straight guide groove 713a for the focus lens 702 is formed in the optical axis direction. Cam rollers 717a and 717b that project radially outward are fixed with axial screws 718 on a rear lens barrel 716 that holds the focus lens 702, and the cam roller 717a is fitted in the straight guide groove 713a.
[0215] The cam ring 715 is rotatably installed in the inner periphery of the straight guide cylinder 713. The relative movement of the straight guide cylinder 713 and the cam ring 715 with respect to the optical axis direction is restricted by the configuration in which the rollers 719 fixed to the cam ring 715 are fitted in the peripheral grooves 713b of the straight guide cylinder 713. The cam grooves 715a for the focusing lens 702 are formed in the cam ring 715, and the above-mentioned cam rollers 717b are simultaneously fitted in the cam grooves 715a.
[0216] On the outer periphery side of the fixing cylinder 712, a rotation transmission ring 720 is provided which is held by a ball track 727 pivotably fixed to the fixing cylinder 712. In the rotation transmission ring 720, a runner 722 is rotatably held on a shaft 720f extending radially from the rotation transmission ring 720, and a large diameter portion 722a of the runner 722 is in contact with a mounting side end face 724b of the manual focus ring 724. A small diameter portion 722b of the runner 722 is in contact with an engaging member 729. Six runners 722 are provided at equal intervals on the outer periphery of the rotation transmission ring 720, and each runner is configured to satisfy the above-mentioned relationship.
[0217] A low friction sheet (washer member) 733 is provided on the inner periphery portion of the manual focus ring 724, and the low friction sheet is sandwiched between the mounting side end face 712a of the fixing cylinder 712 and the front side end face 724a of the manual focus ring 724. The outer peripheral face of the low friction sheet 733 is annular and is in circumferential fit with the inner periphery 724c of the manual focus ring 724, which is in circumferential fit with the outer periphery portion 712b of the fixing cylinder 712. The low friction sheet 733 functions to reduce friction in a rotation ring mechanism having a configuration in which the manual focus ring 724 rotates with respect to the fixing cylinder 712 about the optical axis.
[0218] A pressing force is applied by the force applied by the wave washer 726, such that each of the large diameter portions 722a of the runners 722 and the mounting side end face 724b of the manual focus ring are in contact with each other to press the ultrasonic motor 725 toward the front side of the lens. Likewise, a moderate pressing force is applied by the force applied by the wave washer 726, such that each of the small diameter portions 722b of the runners 722 and the engaging member 729 are in contact with each other to press the ultrasonic motor 725 toward the front side of the lens. The movement of the wave washer 726 in the mounting direction is regulated by the washer 732 which is bayonet connected to the fixing cylinder 712, and the spring force (thrust) generated by the wave washer 726 is transmitted to the ultrasonic motor 725 and further to the runners 722, and also functions as the force by which the manual focus ring 724 presses the mounting side end face 712a of the fixing cylinder 712. That is, the manual focus ring 724 is introduced in such a manner that the manual focus ring 724 is pressed onto the mounting side end face 712a of the fixing cylinder 712 via the low friction sheet 733.
[0219] Therefore, when the ultrasonic motor 725 is rotationally driven against the fixing cylinder 712 by a control portion not shown, each of the rotation wheels 722 rotates around the center of the corresponding shaft 720f due to the frictional contact of the engagement members 729 with the small-diameter portions 722b of the rotation wheels 722. The rotation of each of the rotation wheels 722 around the corresponding shaft 720f causes the rotation transmission ring 720 to rotate around the optical axis (autofocus operation).
[0220] When a rotational force around the optical axis is applied to the manual focus ring 724 from a manual operation input portion not shown, each of the rotation wheels 722 rotates around the corresponding shaft 720f due to the pressure contact of the mounting side end surface 724b of the manual focus ring 724 with the large-diameter portions 722a of the rotation wheels 722 by the frictional force. When the large-diameter portions 722a of each of the rotation wheels 722 rotate around the corresponding shaft 720f, the rotation transmission ring 720 rotates around the optical axis. At this time, the frictional holding force provided by the rotor 725c and the stator 725b does not allow the ultrasonic motor 725 to rotate (manual focus operation).
[0221] The two focus keys 728 are attached to the rotation transmission ring 720 at positions opposite to each other, and each of the focus keys 728 is fitted in a notch portion 715b provided at the end of the cam ring 715. Therefore, when the rotation transmission ring 720 is rotated around the optical axis by the autofocus operation or the manual focus operation, a rotational force is transmitted to the cam ring 715 via the focus keys 728. When the cam ring rotates around the optical axis, the rear lens barrel 716, whose rotation is restricted by the cam roller 717a and the straight guide groove 713a, is allowed to advance or retreat along the cam groove 715a of the cam ring 715 by the cam roller 717b. This drives the focus lens 702, so that the focus operation works.
[0222] Although the interchangeable lens barrel of the single-lens reflex camera is described as the optical apparatus of the present application, the optical apparatus of the present application can be applied to any optical apparatus in various cameras such as compact cameras, electronic still cameras, and personal digital assistants with cameras, including the ultrasonic motor in the driving portion.
[0223] (Vibration device and dust removing device)
[0224] The vibration device of the present application includes a vibration portion having a vibration plate provided with the above-described piezoelectric element. With this configuration, it is possible to provide a vibration device having vibration capability equivalent to or higher than that in the case of using a piezoelectric element containing lead.
[0225] For example, a vibration device for transporting or removing particles, powder, or droplets is widely used in electronic devices and the like.
[0226] A dust removing device having the vibration device of the present application is described below as an example of the vibration device of the present application.
[0227] The dust removing device according to the present application includes a vibration device in the vibration section. With this configuration, a dust removing device can be provided, which has a dust removing efficiency equivalent to or higher than that in the case of using a lead-containing piezoelectric element.
[0228] Figure 12A and Figure 12B are schematic diagrams showing modes of the dust removing device according to the present application. The dust removing device 310 is composed of a plate-shaped piezoelectric element 330 and a vibration plate 320. The material of the vibration plate 320 is not limited, and in the case where the dust removing device 310 is used for an optical device, a semi-transparent material or a light-reflecting material can be used for the vibration plate 320.
[0229] Figure 13A to Figure 13C are schematic diagrams showing the configuration of each piezoelectric element 330 in Figure 12A and Figure 12B . Figure 13A and Figure 13C respectively show the configuration of the front surface and the back surface of each piezoelectric element 330, Figure 13B show the configuration of the side surface of each piezoelectric element 330. As shown in Figure 12A , each piezoelectric element 330 is composed of a single crystal 331, a first electrode 332, and a second electrode 333, and the first electrode 332 and the second electrode 333 are arranged to face the plate surface of the single crystal 331.
[0230] In Figure 13B , the surface provided with the first electrode 332 on the front side of the piezoelectric element 330 is defined as the first electrode surface 336; and in Figure 13A , the surface provided with the second electrode 333 on the front side of the piezoelectric element 330 is defined as the second electrode surface 337.
[0231] Here, the term "electrode surface" in the present application refers to the surface of the piezoelectric element on which an electrode is provided; for example, as shown in Figure 13A and Figure 13B , the first electrode 332 can bypass the second electrode surface 337.
[0232] As shown in Figure 12A and Figure 12B , the piezoelectric element 330 and the vibration plate 320 are firmly fixed together, and the first electrode surface 336 of each piezoelectric element 130 is arranged on the plate surface of the vibration plate 320. By driving the piezoelectric element 330, stress is generated between the piezoelectric element 330 and the vibration plate 320, thereby generating out-of-plane vibration of the vibration plate. The dust removing device 310 according to the present application is a device for removing dust and the like foreign matter adhering to the surface of the vibration plate 320 by the out-of-plane vibration of the vibration plate 320. The term "out-of-plane vibration" refers to elastic vibration that causes the vibration plate to displace in the optical axis direction (i.e., the thickness direction of the vibration plate).
[0233] Figure 14A and Figure 14B is a schematic diagram showing the vibration principle of the dust removing device 310 of the present application. Figure 14A A case in which the vibration plate 320 is made to generate out-of-plane vibration by applying a same-phase alternating voltage to a pair of left and right piezoelectric elements 330 is shown. The polarization direction of a single crystal constituting each of the left and right piezoelectric elements 330 is the same as the thickness direction of the piezoelectric element 330, and the dust removing device 310 is driven in a seventh vibration mode. Figure 14B A case in which the vibration plate 320 is made to generate out-of-plane vibration by applying an opposite-phase alternating voltage in which the phases are opposite to each other by 180° to a pair of left and right piezoelectric elements 330 is shown. The dust removing device 310 is driven in a sixth vibration mode. The dust removing device 310 of the present application is a device capable of efficiently removing dust adhering to the surface of the vibration plate by using at least two different vibration modes.
[0234] (camera)
[0235] The camera of the present application is a camera including at least the above-described dust removing device and the imaging element unit, in which the vibration plate of the dust removing device is disposed on the light-receiving surface side in the imaging element unit. By this configuration, it is possible to provide a camera having dust removing function equivalent to or higher than that in the case of using a lead-containing piezoelectric element. Figure 15 and Figure 16 is a diagram showing a digital single-lens reflex camera as an example of an embodiment of the camera of the present application.
[0236] Figure 15 is a front perspective view of the camera body 601 viewed from the subject side, in which the photographing lens unit has been removed. Figure 16 is an exploded perspective view showing a schematic configuration of the inside of the camera for describing the peripheral structure of the dust removing device and the imaging unit 400 of the present application.
[0237] In the camera body 601, a mirror chamber 605 is provided, through which photographing light flux passing through a photographing lens is introduced, and a main mirror (quick return mirror) 606 is disposed inside the mirror chamber 605. The main mirror 606 can take a state in which the angle with the photographing optical axis is kept at 45° in the direction in which the photographing light flux is introduced to a pentagonal mirror (not shown) and a state in which the main mirror 606 is kept at a position deviated from the photographing light flux in the direction in which the photographing light flux is introduced to an imaging element (not shown).
[0238] On the subject side of the main chassis 300 serving as a skeleton of a camera body, a lens barrel 605 and a shutter unit 200 are arranged in order from the subject side downward. On the photographer side of the main chassis 300, a camera unit 400 is arranged. The camera unit 400 is provided to adjust a photographing surface of a photographing element to a specific distance from a mounting surface of the mounting portion 602 as a reference of a photographing lens unit to be mounted, and to be parallel to the mounting surface.
[0239] Although a digital single-lens reflex camera has been described here as the image pickup apparatus of the present application, the image pickup apparatus of the present application can be a photographing lens unit replaceable camera, such as a mirrorless digital single-lens camera, which does not include the lens barrel 605. The image pickup apparatus of the present application can be applied to a photographing lens unit replaceable camera, various image pickup apparatuses, such as a copier, a facsimile, and a scanner, and electronic equipment including an image pickup apparatus and particularly requiring removal of dust adhering to a surface of an optical member. The camera unit 400 can be used as the photographing element unit of the present application.
[0240] (Ultrasonic probe)
[0241] The ultrasonic probe of the present application includes the piezoelectric element described above, in which the ultrasonic probe transmits and receives signals through the piezoelectric element. With this configuration, it is possible to provide an ultrasonic probe whose transmission / reception performance is equivalent to or higher than that in the case of using a piezoelectric element containing lead.
[0242] Figure 17 is a schematic cross-sectional view showing a mode of the ultrasonic probe of the present application.
[0243] Figure 17 The ultrasonic probe 1100 in is configured with a piezoelectric element 1101, a backing material 1102, an acoustic matching layer 1103, and an acoustic lens 1104. As shown in Figure 17 a plurality of piezoelectric elements 1101 are arranged and adhered to the backing material 1102, and the acoustic matching layer 1103 for matching acoustic impedance is provided on the opposite side surface to serve as a transmission / reception surface.
[0244] The acoustic matching layer 1103 can be a single layer or a plurality of layers, and can be two or more layers. As a material of the acoustic matching layer 1103, for example, carbon, aluminum, an aluminum alloy (e.g., Al-Mg alloy), a magnesium alloy, Macor glass, glass, fused quartz, copper graphite, polyethylene, polypropylene, polycarbonate, ABC resin, polyphenylene ether, ABS resin, AAS resin, AES resin, nylon, polyamide imide, polyethylene terephthalate, polycarbonate, epoxy resin, or polyurethane resin can be used.
[0245] For the backing material 1102, a thermoplastic resin such as natural rubber, ferrite rubber, epoxy resin, polyvinyl chloride, polyvinyl butyral, ABS resin, polyurethane, polyvinyl alcohol, polyethylene, polypropylene, polyacetal, polyethylene terephthalate, fluororesin, polyethylene glycol, and polyethylene terephthalate, or a mixture of any thermoplastic material and a metal powder, or a carbide material such as tungsten carbide can be used.
[0246] The piezoelectric elements 1101 can be integrated together or separated into multiple parts. Figure 17 An example is shown in which the piezoelectric elements 1101 are provided as separate parts. A flexible cable (not shown) is connected to the electrodes of each piezoelectric element, and can input and output signals transmitted and received by the piezoelectric elements. An acoustic lens 1104 is adhered to the acoustic matching layer 1103. The acoustic lens 1104 is a member for converging ultrasonic waves transmitted from the piezoelectric elements 1101 to an object, and in Figure 17 an example, is curved. For the material of the acoustic lens 1104, for example, a rubber containing silicone (rubber) as a main component is generally used.
[0247] In use of the ultrasonic probe 1100, an alternating voltage is applied to the piezoelectric elements 1101 by a flexible cable, the piezoelectric elements are vibrated by a piezoelectric effect, and thus the piezoelectric elements 1101 transmit ultrasonic waves. At this time, if the acoustic impedance of an object on which the ultrasonic waves hit is small, or the ultrasonic waves hit the object via water or air, the presence of the acoustic matching layer 1103 can prevent a reflected wave from being generated due to a large change in acoustic impedance, and thus the object can be efficiently irradiated with ultrasonic waves. In reception, ultrasonic waves reflected inside the object vibrate the piezoelectric elements 1101, and the vibrations are electrically converted by a piezoelectric effect to obtain a reception signal. Although conversion between electric energy and mechanical energy is performed in transmission and reception, the conversion efficiency at the time depends on the size of the electromechanical coupling coefficient.
[0248] (Ultrasonic diagnostic apparatus)
[0249] The ultrasonic diagnostic apparatus of the present application includes at least the above-described ultrasonic probe and an image output section (also referred to as an image display section). With this configuration, an ultrasonic diagnostic apparatus can be provided whose driving efficiency is equivalent to or higher than that in the case of using a lead-containing piezoelectric element. Figure 18 is a schematic diagram showing a mode of the ultrasonic diagnostic apparatus of the present application. Figure 18The ultrasonic diagnostic apparatus 1110 in the present invention is equipped with an ultrasonic probe 1100, a cable 1111, a drive control unit 1113, an image display unit 1112, and an image processing unit 1114. The flexible cable of the ultrasonic probe 1100 and the drive control unit 1113 is connected via the cable 1111. AC voltage is applied from the drive control unit 1111 to the piezoelectric element 1101 of the ultrasonic probe 1100 via the cable 1111. When the interior of a subject is irradiated with ultrasonic waves from the ultrasonic probe 1100, the ultrasonic waves reflected from the subject's interior are converted back into electrical signals in the ultrasonic probe 1100 and input to the image processing unit 1114 via the cable 1111. The image processing unit 1114 calculates the delay time and signal strength change of the AC voltage output from the drive control unit 1113 to generate image data. The generated image data is output to the image display unit 1112.
[0250] (Ultrasound diagnostic system)
[0251] The ultrasonic diagnostic system of the present invention includes the ultrasonic probe described above; a transmitter that transmits the signal output from the ultrasonic probe; and a receiver that receives the signal transmitted from the transmitter. This configuration provides an ultrasonic diagnostic system with a driving efficiency comparable to or higher than that achieved using a lead-containing piezoelectric element. Figure 19 and Figure 20 Schematic diagram showing the mode of the ultrasonic diagnostic system of the present invention. Figure 19 In the ultrasonic diagnostic system 1120, the signal acquired by the ultrasonic probe 1100 is transmitted from the transmitting unit 1121 and received by the receiving unit 1122. The image processing unit 1114 generates image data from the received signal and outputs the image data to the image display unit 1112. The transmitting unit 1121 and the receiving unit 1122 may be remote from each other. Transmission and reception can be performed via radio communication such as Wi-Fi (R) and Bluetooth (R) or via a network line with a connected network cable.
[0252] exist Figure 20 In the ultrasonic diagnostic system 1120 in FIG. 1 , the image processing unit 1114 generates image data from the output signal, the data is transmitted as a signal from the transmitting unit 1121 , and the signal is received by the receiving unit 1122 . The received signal is output to the image display unit 1112 .
[0253] (Electronic equipment)
[0254] Next, an electronic device of the present application will be described. The electronic device of the present application is provided with a piezoelectric acoustic member including the above-described piezoelectric element or the above-described laminated piezoelectric element. With this configuration, an electronic device can be provided, which has sound generation performance equivalent to or higher than that in the case of using a lead-containing piezoelectric element. The piezoelectric acoustic member includes a speaker, a buzzer, a microphone, and a surface acoustic wave (SAW) element.
[0255] Figure 21 is an overall perspective view of a body 931 of a digital camera, which is an example of an embodiment of the electronic device of the present application, as viewed from the front of the body 931. On the front surface of the body 931, an optical device 901, a microphone 914, a flash light emitting section 909, and an illuminating section 916 are arranged. The microphone 914 is introduced into the inside of the body, and thus is indicated by a broken line. In front of the microphone 914, a hole for picking up sound from the outside is provided.
[0256] On the top surface of the body 931, a power button 933 for performing a focusing operation, a speaker 912, a zoom lever 932, and a release button 908 are provided. The speaker 912 is introduced into the inside of the body 931, and thus is indicated by a broken line. In front of the speaker 912, a hole for transmitting sound to the outside is provided.
[0257] The piezoelectric acoustic member of the present application is used for at least one of the microphone 914, the speaker 912, and a surface acoustic wave element.
[0258] Although the digital camera has been described as the electronic device of the present application, the electronic device of the present application can also be applied to various electronic devices including a piezoelectric acoustic member, such as an audio player, a sound recorder, a cell phone, and an information terminal.
[0259] As described above, the piezoelectric element of the present application can be used for an ultrasonic motor, an optical device, a vibration device, a dust removing device, an imaging device, an ultrasonic probe, an ultrasonic diagnostic device, and an electronic device.
[0260] In addition to the above-described devices, the single crystal and the piezoelectric element of the present application can also be used for devices including a motor, a discharge head, a discharge device, a piezoelectric actuator, a piezoelectric sensor, and a ferroelectric memory.
[0261] According to the present application, a method for manufacturing a single crystal having a high electromechanical coupling coefficient and a high coercive field, and a single crystal, in which the single crystal cannot be produced by any conventional production method, are provided.
[0262] EMBODIMENT
[0263] Hereinafter, the present application will be described in more detail with reference to Examples, but the present application is not limited by the following Examples.
[0264] The single crystal and piezoelectric element of the present application is produced by the method shown below.
[0265] (Example 1)
[0266] As the raw material powders, barium titanate (BaTi03, Ba / Ti = 0.999), barium zirconate (BaZr03, Ba / Zr = 1.002), trimanganese tetroxide (Mn304), and titanium oxide were used to adjust the ratio a of the sum of the number of moles of Ti and Zr to the sum of the number of moles of Ba. These raw material powders were weighed to obtain a composition corresponding to the Ba(Ti 0.985 (Ti 0.93 , Zr 0.07 )03 phase in a ratio of 1.0:1.0:0.1. With respect to 100 parts by mass of the oxide, Mn was added so that the Mn content was 0.12 parts by mass in terms of metal. In addition, the oxide to which Mn had been added was mixed by dry mixing with a ball mill for 24 hours. To granulate the resulting mixed powder, 3 parts by mass of a PVA binder was attached to the surface of the mixed powder with respect to the amount of the mixed powder using a spray drier.
[0267] Next, the resulting granulated powder was filled into a metal mold in which the surface of the sample side was mirror finished, and a molding pressure of 200 MPa was applied with a press molding machine to produce two cuboid molded bodies. These molded bodies can be further pressed by using a cold isostatic press molding machine.
[0268] Next, one of the molded bodies was placed as a sample on a heating stage of a microscope (manufactured by Linkam Scientific Instruments Ltd.) and the temperature was raised, and the surface of the substrate 12 was observed with a microscope, and it was found that the liquid phase appearance temperature was 1320°C and the liquid phase disappearance temperature was 1385°C.
[0269] Next, the other molded body was placed in an electric furnace and kept at a maximum temperature of 1300°C for 5 hours and sintered in an atmospheric atmosphere for 24 hours to obtain a cubic substrate 12 of 12 mm x 18 mm x 1.3 mm.
[0270] Next, each face of the obtained cubic substrate was polished using a polisher having a plurality of abrasive grains different in roughness to obtain a thickness of 1.0 mm, and finally chemical polishing was performed as finish machining to obtain a mirror surface.
[0271] Next, a zirconia-coated alumina crucible was prepared as the crucible 17, a zirconia setter as the setter 16, a zirconia setter (size: 50 mm x 50 mm x 1 mm, weight: 20 g) as the weight 14, and a zirconia bead as the bead 15 were placed as shown in Figure 6 Next, a zirconia-coated alumina crucible was prepared as the crucible 17, a zirconia setter as the setter 16, a zirconia setter (size: 50 mm x 50 mm x 1 mm, weight: 20 g) as the weight 14, and a zirconia bead as the bead 15 were placed as shown in Figure 7The shown is placed in an electric furnace covered with a lid 18 and fired.
[0272] The seed single crystal 11 used here was a 10 mm x 10 mm x 1 mm BaTiO 3 (manufactured by Physcience Opto-electronics Co., Ltd.) substrate whose principal surface and side surfaces were all (100) planes and each surface was mirror-polished.
[0273] The temperature rise profile during firing is as follows: a first temperature rise, in which the temperature was raised from room temperature to 1320°C (the temperature at which the liquid phase appears) at a heating rate of 150°C / h over 8.8 hours, followed by a second temperature rise, in which the temperature was raised from 1320°C to 1385°C (the temperature at which the liquid phase disappears) at a heating rate of 0.65°C / h over 100 hours; thereafter, the temperature was held at 1385°C for 300 hours; finally, the temperature was lowered to room temperature by cooling the resultant. The first temperature rise, second temperature rise, and firing were performed in the atmosphere.
[0274] Observation of the fired substrate with an optical microscope confirmed that the single crystal growth portion (region extended from the seed single crystal) was a single crystal without any grain boundaries.
[0275] Next, the seed single crystal 11 portion is removed by grinding, and the single crystal portion is cut out using a dicing saw to obtain a first single crystal.
[0276] Next, the crystal structure of the first single crystal was analyzed by X-ray diffraction. As a result of the analysis, only a peak corresponding to the perovskite type (100) oriented single crystal was observed.
[0277] Next, if Figure 2 As shown, the first single crystal is placed on a stable zirconia placer 6, and the resultant is placed on Figure 1 The reduction firing furnace was placed in a high-temperature electric furnace and fired at 1340° C. for 5 hours in a reducing atmosphere, and the temperature was finally lowered to room temperature by cooling the resultant.
[0278] The reducing atmosphere used was argon containing 3 mol% hydrogen in a gas cylinder, and the oxygen partial pressure immediately before firing was 5×10 -15 Pa.
[0279] Next, the crystal structure of the single crystal fired in a reducing atmosphere was analyzed by X-ray diffraction. As a result of the analysis, no heterogeneous phase different from the crystal of perovskite was observed. Figure 3The first single crystal 1 fired under a reducing atmosphere was placed in the retort 7, the resultant was placed on the stabilized zirconia holder 6, the resultant was covered with a lid and placed in an electric furnace, fired at 1000°C in an atmospheric atmosphere for 10 hours, and finally the temperature was decreased to room temperature by cooling the resultant; thus, a single crystal was prepared. At the time of firing, a super electric furnace SSFT-1520 (manufactured by YAMADA DENKI CO., LTD.) was used.
[0280] Next, the crystal structure of the prepared single crystal was analyzed by X-ray diffraction. The results are shown in FIG. 3. From the (110) pole figure and the (200) pole figure, the (100) orientation was observed. In addition, each side surface of the sample was a (200) plane. Figure 22
[0281] Next, the composition of the single crystal was obtained and evaluated by ICP emission spectroscopy. The results are shown in Table 1. For Ba, Ti, Zr, and Mn, the weighed composition and the composition after firing were consistent with each other. Pb was not detected.
[0282] Next, the single crystal was processed into a 0.8 mm x 0.8 mm x 5.0 mm prism by grinding and cutting. At that time, the processing was performed in such a manner that the crystal orientation of the 0.8 mm x 0.8 mm face corresponded to (100).
[0283] Next, a gold electrode having a thickness of 400 nm was formed on each 0.8 mm x 0.8 mm face by a DC sputtering method; thus, a piezoelectric element of the present application was prepared.
[0284] Between each electrode and the single crystal, a 30 nm titanium film was formed as a close adhesion layer. In the DC sputtering, the 0.8 mm x 5.0 mm side face was subjected to masking to avoid attachment of the gold electrode.
[0285] Next, the obtained piezoelectric element was subjected to polarization treatment by applying an electric field of 1 kV / mm for 30 minutes on a hot plate having a surface temperature set to 60°C to 100°C.
[0286] Next, at room temperature (25°C), the electromechanical coupling coefficient k 33 of the piezoelectric element including the single crystal of the present application was evaluated by a resonance-anti-resonance method using an impedance analyzer (4294A manufactured by Agilent Technologies).
[0287] The evaluation results showed that the electromechanical coupling coefficient k 33 of the sample was 83%. It was found that the electromechanical coupling coefficient of the lead-free piezoelectric material was large.
[0288] Next, when the temperature of the sample was changed from 0°C to 70°C at a rate of 0.5°C per minute, a measurement was made every 5°C, and the rate of change of the piezoelectric constant d and the maximum value of the relative dielectric constant ε in the temperature range from 0°C to 70°C were obtained according to the following equations (5) and (6) 33
[0289]
[0290] d 33 Rate of change (%) = 100 x (d 33MAX - d 33MIN ) / d 33@0 °C (6).
[0291] The results are shown in Table 1 and Figure 25 and Figure 26 Here, ε T represents the dielectric constant, and the dielectric constant divided by the dielectric constant of vacuum corresponds to the relative dielectric constant.
[0292] It was found as a result that the change in d 33 was small and the maximum value of the relative dielectric constant ε 33 of the single crystal was small.
[0293] Next, the coercive field of the piezoelectric element was evaluated. By using a ferroelectric / piezoelectric evaluation system (LC II manufactured by Radiant Technologies, Inc.), the electric field at which the polarization was 0 was read from the PE hysteresis curve given by the degree of polarization with respect to the electric field in the hysteresis measurement mode in the Figure 24 , and this value was taken as the coercive field. In this case, the coercive field was 4.0 kV / cm.
[0294] (Example 2)
[0295] The single crystal and the piezoelectric element of the present application were produced by the same process as in Example 1 except that the firing temperature under a reducing atmosphere was changed to 1385°C as shown in Table 1.
[0296] Subsequently, the composition, the electromechanical coupling coefficient k 33 , the coercive field, the maximum value of the relative dielectric constant from 0°C to 70°C, and the rate of change of the piezoelectric constant of the single crystal of the present application were evaluated by the same procedure as in Example 1. The results are shown in Table 1.
[0297] (Example 3)
[0298] As the raw material powders, barium titanate (BaTi03, Ba / Ti = 0.999), barium zirconate (BaZr03, Ba / Zr = 1.002), trimanganese tetroxide (Mn304), bismuth oxide (Bi203), lithium carbonate (Li2C03), and titanium oxide were used to adjust the ratio, a, of the sum of the number of moles of Ti and Zr to the sum of the number of moles of Ba. These raw material powders were weighed to obtain a composition formula Ba 0.990 (Ti 0.98 , Zr 0.02 )03corresponding to the proportions.
[0299] With respect to 100 parts by mass of the oxide, trimanganese tetroxide (Mn304), bismuth oxide (Bi203), and lithium carbonate (Li2C03) were added so that the Mn content was 0.23 parts by mass in terms of metal, the Bi content was 0.18 parts by mass in terms of metal, and the Li content was 0.15 parts by mass in terms of metal. Further, the oxide to which Mn304, Bi203, and Li2C03had been added was mixed by dry mixing with a ball mill for 24 hours. In order to granulate the resulting mixed powder, a PVA binder in an amount of 3 parts by mass with respect to the amount of the mixed powder was attached to the surface of the mixed powder using a spray dryer.
[0300] Next, the resulting granulated powder was filled into a metal mold in which the surface of the sample side had been mirror-polished, and a molding pressure of 200 MPa was applied with a press molding machine to produce two cuboid molded bodies. These molded bodies can be further pressed by using a cold isostatic press molding machine.
[0301] Next, one of the molded bodies was placed as a sample on a heating stage of a microscope (manufactured by Linkam Scientific Instruments Co., Ltd.) and the temperature was raised, and microscopic observation was performed on the surface of the substrate 12, and it was found that the liquid phase appearance temperature was 1320°C and the liquid phase disappearance temperature was 1400°C.
[0302] Next, the other molded body was placed in an electric furnace and maintained at a maximum temperature of 1300°C for 5 hours and sintered in an atmospheric atmosphere for 24 hours to obtain a cubic substrate 12 of 12 mm x 18 mm x 1.3 mm.
[0303] Next, each face of the obtained cubic substrate was polished using a polisher having a plurality of abrasive grains having different roughnesses to obtain a thickness of 1.0 mm, and finally chemical polishing was performed as finish machining to obtain a mirror surface.
[0304] Next, a zirconia-coated alumina crucible was prepared as the crucible 17, a zirconia setter as the setter 16, a zirconia setter (size: 50 mm x 50 mm x 1 mm, weight: 20 g) as the weight 14, and a zirconia bead as the bead 15, and placed in a furnace covered with a lid 18 as shown in Figure 6 , and fired. Figure 7
[0305] The seed single crystal 11 used here was a BaTiO3 (manufactured by Physcience Opto-electronics Co., Ltd.) substrate of 10 mm x 10 mm x 1 mm, with both the main surface and the side surface being (100) planes, and each surface being mirror-polished.
[0306] The temperature increase curve during firing was as follows: a first temperature increase, in which the temperature was increased from room temperature to 1320°C, which is the liquid phase appearance temperature, at a temperature increase rate of 150°C / h for 8.8 hours, followed by a second temperature increase, in which the temperature was increased from 1320°C to 1400°C, which is the liquid phase disappearance temperature, at a temperature increase rate of 0.80°C / h for 100 hours; thereafter, the temperature was maintained at 1400°C for 1000 hours; and finally, the temperature was decreased to room temperature by cooling the resultant. The first temperature increase, the second temperature increase, and the firing were performed in the atmosphere.
[0307] Observation of the fired substrate with an optical microscope confirmed that the single crystal growth portion (the region extending from the seed single crystal) was a single crystal without any grain boundaries.
[0308] Next, the seed single crystal 11 portion was removed by polishing, and a single crystal portion was cut out with a dicing saw, to obtain a first single crystal.
[0309] Next, the crystal structure of the first single crystal was analyzed by X-ray diffraction. As a result of the analysis, only peaks corresponding to a perovskite-type (100)-oriented single crystal were observed.
[0310] Next, the first single crystal was placed on the stable zirconia setter 6 as shown in Figure 2 , the resultant was placed in the high-temperature electric furnace of the reduction firing furnace as shown in Figure 1 , and fired at 1280°C in a reducing atmosphere for 5 hours, and finally the temperature was decreased to room temperature by cooling the resultant.
[0311] The atmosphere gas of the reducing atmosphere used was argon gas containing 3 mol% hydrogen gas in a gas cylinder, and the oxygen partial pressure immediately before firing was 5 x 10 -15 Pa.
[0312] Next, the crystal structure of the single crystal fired in a reducing atmosphere was analyzed by X-ray diffraction. As a result of the analysis, no heterogeneous phase of the crystal different from that of perovskite was observed. Figure 3 As shown, a first single crystal 1 fired in a reducing atmosphere is placed in a sagger 7, the resultant is placed on a stable zirconia holder 6, the resultant is covered with a lid and placed in an electric furnace, fired in an atmosphere at 1000°C for 10 hours, and finally cooled to room temperature; thus, a single crystal is produced. During firing, a super electric furnace SSFT-1520 (manufactured by YAMADA DENKI CO., LTD.) is used.
[0313] Next, the crystal structure of the prepared single crystal was analyzed by X-ray diffraction. Figure 23 As shown in Figure 2, the (100) orientation is observed from the (110) pole diagram and the (200) pole diagram.
[0314] Next, the composition of the single crystal was obtained and evaluated by ICP emission spectroscopy. The results are shown in Table 1. For Ba, Ti, Zr, Mn, and Bi, the weighed composition and the composition after firing were consistent with each other. No Pb was detected.
[0315] Next, the single crystal was processed into a prism of 0.8 mm × 0.8 mm × 5.0 mm by grinding and cutting. At that time, the processing was performed so that the crystal orientation of the 0.8 mm × 0.8 mm plane corresponded to (110).
[0316] Next, a gold electrode having a thickness of 400 nm was formed on each surface of 0.8 mm×0.8 mm by a DC sputtering method; thereby, the piezoelectric element of the present invention was prepared.
[0317] A 30nm thick titanium film was formed between each electrode and the single crystal as a close adhesion layer. The 0.8mm x 5.0mm side surface was masked in DC sputtering to prevent the gold electrode from adhering.
[0318] Next, the obtained piezoelectric element was subjected to polarization treatment by applying an electric field of 1 kV / mm for 30 minutes on a hot plate whose surface temperature was set at 60° C. to 100° C.
[0319] Next, the electromechanical coupling coefficient k of the piezoelectric element including the single crystal of the present invention was evaluated by the resonance-antiresonance method using an impedance analyzer (4294A manufactured by Agilent Technologies) at room temperature (25°C). 33 .
[0320] The evaluation results show that the electromechanical coupling coefficient k of the sample is 33 It was found that the electromechanical coupling coefficient of the lead-free piezoelectric material was large.
[0321] Next, when the temperature of the sample is changed from 0°C to 70°C at a rate of 0.5°C per minute, measurements are taken every 5°C. The rate of change of the piezoelectric constant d and the relative dielectric constant ε in the temperature range of 0°C to 70°C are obtained according to the above equations (5) and (6). 33 The maximum value of:
[0322] The results are shown in Table 1 and Figure 25 as well as Figure 26 Here, ε T represents the dielectric constant, which is divided by the dielectric constant of a vacuum, corresponding to the relative dielectric constant.
[0323] The results showed that d 33 The change in the relative dielectric constant ε of the single crystal is small and 33 The maximum value of is small.
[0324] Next, the coercive field of the piezoelectric element was evaluated. By using a ferroelectric / piezoelectric evaluation system (LC II manufactured by Radiant Technologies, Inc.), Figure 24 In the hysteresis measurement mode in , the electric field at which the polarization is zero is read from the PE hysteresis curve given by the polarization relative to the electric field, and this value is regarded as the coercive field. In this case, the coercive field is 7.5 kV / cm.
[0325] (Comparative Example 1)
[0326] As raw material powders, barium titanate (BaTiO3, Ba / Ti=0.999), barium zirconate (BaZrO3, Ba / Zr=1.002), trimanganese tetraoxide (Mn3O4) and titanium oxide having an average particle size of 100 nm were used to adjust the ratio of the total number of moles of Ti and Zr to the total number of moles of Ba. These raw material powders were weighed to obtain a composition formula Ba containing titanium and barium as main components. 0.985 (Ti 0.93 , Zr 0.07 )O3 in a corresponding ratio. Mn was added to 100 parts by mass of the oxide to a Mn content of 0.12 parts by mass, calculated as metal. Furthermore, the Mn-added oxide was mixed by dry mixing in a ball mill for 24 hours. To granulate the resulting mixed powder, 3 parts by mass of a PVA binder, relative to the mixed powder, was applied to the surface of the mixed powder using a spray dryer.
[0327] Next, a metal mold in which the surface on the sample side was mirror-polished was filled with the obtained granulated powder, and a molding pressure of 200 MPa was applied with a press molding machine to produce two rectangular parallelepiped molded bodies.
[0328] Next, one of the shaped bodies was placed as a sample on a heating stage (manufactured by Linkam Scientific Instruments Ltd.) of a microscope, and the temperature was raised, and the surface of the substrate 12 was observed with a microscope, and it was found that the liquid phase appeared at 1320°C and disappeared at 1385°C.
[0329] Next, the other shaped body was placed in an electric furnace, and maintained at a maximum temperature of 1300°C for 5 hours, and sintered in an atmosphere for 24 hours to obtain a cubic substrate 12 of 12 mm x 18 mm x 1.3 mm.
[0330] Next, each face of the obtained cubic substrate was polished using a polisher having a plurality of abrasive grains having different roughnesses to obtain a thickness of 1.0 mm, and finally, chemical polishing was performed as finishing to obtain a mirror surface.
[0331] Next, a zirconia-coated alumina crucible was prepared as the crucible 17, a zirconia setter as the setter 16, a zirconia setter (size: 50 mm x 50 mm x 1 mm, weight: 20 g) as the weight 14, and a zirconia bead as the bead 15, and placed as shown in Figure 6 , and placed in an electric furnace covered with a lid 18 as shown in Figure 7 , and fired.
[0332] The seed single crystal 11 used here was a BaTiO3 substrate (manufactured by Physcience Opto-electronics Co., Ltd.) of 10 mm x 10 mm x 1 mm, in which the upper and lower faces and the side faces were (100) planes and each face was mirror-polished.
[0333] The temperature raising curve at the time of firing was as follows: first temperature raising in which the temperature was raised from room temperature to 1320°C which was the liquid phase appearance temperature at a temperature raising rate of 150°C / h for 8.8 hours, and then second temperature raising in which the temperature was raised from 1320°C to 1385°C which was the liquid phase disappearance temperature at a temperature raising rate of 0.65°C / h for 100 hours; thereafter, the temperature was maintained at 1385°C for 300 hours; and finally, the temperature was lowered to room temperature by cooling the obtained product. The first temperature raising, the second temperature raising, and the firing were performed in an atmosphere.
[0334] Observation of the fired substrate 12 with an optical microscope confirmed that the single crystal growth portion (the region extended from the seed single crystal) was a single crystal without any grain boundaries.
[0335] Next, the seed single crystal 11 portion was removed by polishing, and a single crystal portion was cut out with a dicing saw to obtain the first single crystal of Comparative Example 1.
[0336] Next, the crystal structure of the prepared first single crystal was analyzed by X-ray diffraction. From the (110) pole figure and the (200) pole figure, the (100) orientation was observed. In addition, each side surface of the sample was a (200) plane.
[0337] Next, the composition of the single crystal was obtained and evaluated by ICP emission spectroscopy. The results are shown in Table 1. For Ba, Ti, Zr, and Mn, the weighed composition and the composition after firing were consistent with each other. Pb was not detected.
[0338] Next, the single crystal was processed into a 0.8 mm x 0.8 mm x 5.0 mm prism by grinding and cutting. At that time, the processing was performed in a manner in which the crystal orientation of the 0.8 mm x 0.8 mm surface corresponded to (100).
[0339] Next, a gold electrode having a thickness of 400 nm was formed on each 0.8 mm x 0.8 mm surface by a DC sputtering method; thereby a piezoelectric element of Comparative Example 1 was manufactured.
[0340] Between each electrode and the single crystal, a 30 nm titanium film was formed as a close adhesion layer. In the DC sputtering, a mask process was performed on the 0.8 mm x 5.0 mm side surface to avoid the attachment of the gold electrode.
[0341] Next, the obtained piezoelectric element was subjected to a polarization treatment by applying a 1 kV / mm electric field for 30 minutes on a hot plate on which the surface temperature was set to 60°C to 100°C.
[0342] Next, at room temperature (25°C), the electromechanical coupling coefficient k 33 of the piezoelectric element including the single crystal of Comparative Example 1 was evaluated by a resonance-anti-resonance method using an impedance analyzer (4294A manufactured by Agilent Technologies).
[0343] The evaluation results showed that the k 33 of the sample was 79%.
[0344] Next, during the process in which the sample temperature was changed from 0°C to 70°C at a rate of 0.5°C per minute, a measurement was performed every 5°C, and the piezoelectric constant d 33 the rate of change in the temperature range of 0°C or more and less than 70°C, and the maximum value of the relative dielectric constant ε 33 were obtained according to the above-described equations (5) and (6).
[0345] The results are shown in Table 1. Here, ε T represents the dielectric constant, and the dielectric constant divided by the dielectric constant of vacuum corresponds to the relative dielectric constant.
[0346] Next, the coercive field of the piezoelectric element was evaluated. By using a ferroelectric / piezoelectric evaluation system (LC II manufactured by Radiant Technologies, Inc.), the electric field at which the degree of polarization was 0 was read from a PE hysteresis curve given with respect to the degree of polarization of the electric field, and this value was regarded as the coercive field. In this case, the coercive field was 1.6 kV / cm.
[0347] (Comparative Example 2)
[0348] As the raw material powders, barium titanate (BaTi03, Ba / Ti = 0.999), barium zirconate (BaZr03, Ba / Zr = 1.002), trimanganese tetroxide (Mn304), bismuth oxide (Bi203), lithium carbonate (Li2C03), and titanium oxide were used to adjust the ratio a of the total sum of the number of moles of Ti and Zr to the total sum of the number of moles of Ba. These raw material powders were weighed to obtain a composition corresponding to the Ba(Ti 0.990 (Ti 0.98 , Zr 0.02 )03phase in a ratio of 1.0: 1.0: 0.5: 0.5: 0.5: 0.5.
[0349] With respect to 100 parts by mass of the oxide, trimanganese tetroxide (Mn304), bismuth oxide (Bi203), and lithium carbonate (Li2C03) were added so that the Mn content was 0.23 parts by mass as metal, the Bi content was 0.18 parts by mass as metal, and the Li content was 0.15 parts by mass as metal. Further, the oxide to which Mn304, Bi203, and Li2C03had been added was mixed by dry mixing with a ball mill for 24 hours. In order to granulate the resulting mixed powder, a PVA binder in an amount of 3 parts by mass with respect to the amount of the mixed powder was attached to the surface of the mixed powder using a spray dryer.
[0350] Next, the resulting granulated powder was filled into a metal mold in which the surface of the sample side was mirror-polished, and a molding pressure of 200 MPa was applied with a press molding machine to produce two cuboid molded bodies.
[0351] Next, one of the molded bodies was placed as a sample on a heating stage of a microscope (manufactured by Linkam Scientific Instruments Ltd.) and the temperature was raised, and microscopic observation of the surface of the substrate 12 found that the liquid phase appearance temperature was 1320°C and the liquid phase disappearance temperature was 1400°C.
[0352] Next, the other molded body was placed in an electric furnace and kept at a maximum temperature of 1300°C for 5 hours and sintered in an atmosphere for 24 hours to obtain a cubic substrate 12 of 12 mm x 18 mm x 1.3 mm.
[0353] Next, each face of the obtained cubic substrate was polished using a polisher having a plurality of abrasive grains having different roughness to obtain a thickness of 1.0 mm, and finally, chemical polishing was performed as a finishing process to obtain a mirror surface.
[0354] Next, a zirconia-coated alumina crucible was prepared as the crucible 17, a zirconia setter as the setter 16, a zirconia setter (size: 50 mm x 50 mm x 1 mm, weight: 20 g) as the weight 14, and a zirconia bead as the bead 15, and were placed in an electric furnace covered with a lid 18 as shown in Figure 6 Figure 7
[0355] The seed single crystal 11 used here was a BaTiO3 substrate (manufactured by Physcience Opto-electronics Co., Ltd.) of 10 mm x 10 mm x 1 mm, in which the upper and lower faces and the side faces were (100) planes and each face was mirror-polished, and the seed single crystal 11 was placed on the setter 16 as shown in
[0356] The temperature increase curve at the time of firing was as follows: a first temperature increase in which the temperature was increased from room temperature to 1320°C, which is the liquid phase appearance temperature, at a temperature increase rate of 150°C / h for 8.8 hours, followed by a second temperature increase in which the temperature was increased from 1320°C to 1400°C, which is the liquid phase disappearance temperature, at a temperature increase rate of 0.80°C / h for 100 hours; thereafter, the temperature was maintained at 1400°C for 1000 hours; and finally, the temperature was decreased to room temperature by cooling the resultant. The first temperature increase, the second temperature increase, and the firing were performed in the atmosphere.
[0357] Observation of the fired substrate 12 with an optical microscope confirmed that the single crystal growth portion (the region extending from the seed single crystal) was a single crystal having no grain boundary.
[0358] Next, the seed single crystal 11 portion was removed by polishing, and the single crystal portion was cut out with a dicing saw to obtain the single crystal of Comparative Example 2.
[0359] Next, the crystal structure of the prepared single crystal was analyzed by X-ray diffraction. From the (110) pole figure and the (200) pole figure, the (110) orientation was observed.
[0360] Next, the composition of the single crystal was obtained and evaluated by ICP emission spectrometry. The results are shown in Table 1. For Ba, Ti, Zr, Mn, and Bi, the weighed composition and the composition after firing were consistent with each other. Pb was not detected.
[0361] Next, the single crystal was processed into a 0.8 mm x 0.8 mm x 5.0 mm prism by grinding and cutting. At that time, the processing was performed in a manner such that the crystal orientation of the 0.8 mm x 0.8 mm face corresponded to (110).
[0362] Next, a gold electrode having a thickness of 400 nm was formed on each of the 0.8 mm x 0.8 mm faces by a DC sputtering method; thereby a piezoelectric element of Comparative Example 2 was manufactured.
[0363] Between each electrode and the single crystal, a 30 nm titanium film was formed as a close adhesion layer. In the DC sputtering, a mask process was performed on the 0.8 mm x 5.0 mm side face to avoid attachment of the gold electrode.
[0364] Next, the obtained piezoelectric element was subjected to a polarization treatment by applying an electric field of 1 kV / mm for 30 minutes on a hot plate having a surface temperature set to 60°C to 100°C.
[0365] Next, at room temperature (25°C), the electromechanical coupling coefficient k 33 of the piezoelectric element including the single crystal of Comparative Example 2 was evaluated by a resonance-anti-resonance method using an impedance analyzer (4294A manufactured by Agilent Technologies).
[0366] The evaluation result showed that the k 33 of the sample was 75%.
[0367] Next, the piezoelectric constant d 33 in the temperature range of 0°C or higher and 70°C or lower and the maximum value of the relative dielectric constant ε 33 were obtained according to the above-described equations (5) and (6) while the sample temperature was changed from 0°C to 70°C at a rate of 0.5°C per minute, and measurement was performed every 5°C.
[0368] The results are shown in Table 1. Here, ε T represents the dielectric constant, and the dielectric constant divided by the dielectric constant of vacuum corresponds to the relative dielectric constant.
[0369] Next, the coercive field of the piezoelectric element was evaluated. By using a ferroelectric / piezoelectric evaluation system (LC II manufactured by Radiant Technologies, Inc.), the electric field at which the degree of polarization was 0 was read from a PE hysteresis curve given with respect to the degree of polarization, and this value was regarded as the coercive field. In this case, the coercive field was 5.6 kV / cm.
[0370] [Table 1] Table 1
[0371]
[0372] Table 1 (continued)
[0373]
[0374] (Example 4)
[0375] Figure 9 The ultrasonic motor shown was manufactured using the piezoelectric element of Example 1. In the manufactured ultrasonic motor, rotation of the motor in response to application of an alternating voltage was confirmed.
[0376] (Example 5)
[0377] Figure 11 The optical device shown was manufactured using the ultrasonic motor of Example 4. In the manufactured optical device, autofocusing operation in response to application of an alternating voltage was confirmed.
[0378] (Example 6)
[0379] Figure 12A and Figure 12B The dust removing device shown was manufactured using the piezoelectric element of Example 1. When plastic beads were dispersed and an alternating voltage was applied to the manufactured dust removing device, a good dust removal rate was confirmed.
[0380] (Example 7)
[0381] Figure 15 The camera device shown was manufactured using the dust removing device of Example 6. When the manufactured camera device was operated, dust on the surface of the camera unit was well removed, and an image without any dust defects was obtained.
[0382] (Example 8)
[0383] Figure 17 The ultrasonic probe shown was manufactured using the piezoelectric element of Example 1. In the manufactured ultrasonic probe, ultrasonic waves were transmitted by application of an alternating voltage, and a reception signal obtained by reflection from the inside of a subject was confirmed.
[0384] (Example 9)
[0385] Figure 18 The ultrasonic diagnostic device shown was manufactured using the ultrasonic probe of Example 8. When the manufactured ultrasonic diagnostic device was operated, an image of the inside of a subject was clearly output.
[0386] (Example 10)
[0387] Figure 19The ultrasonic diagnostic system shown was manufactured using the ultrasonic probe of Example 8. When the manufactured ultrasonic diagnostic system was operated to display on the image display section, the image of the inside of the subject was clearly output.
[0388] (Example 11)
[0389] Figure 21 The electronic device shown was manufactured using the piezoelectric element of Example 1. In the manufactured electronic device, the speaker operation in response to the application of an alternating voltage was confirmed.
[0390] The single crystal of the present application has an electromechanical coupling coefficient and a high coercive field. Therefore, the single crystal of the present application can be used for various devices including an ultrasonic motor, a dust removing device, and an ultrasonic probe without causing any problems.
[0391] While the present application has been described with reference to exemplary embodiments, it is to be understood that the application is not limited to the disclosed exemplary embodiments. The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A method for producing a perovskite single crystal, comprising: step (1) : firing a raw material containing an acceptor under an atmospheric atmosphere to produce a first single crystal of a perovskite, step (2) : firing the first single crystal under a reducing atmosphere, and step (3) : firing the single crystal produced in step (2) under an atmospheric atmosphere, wherein, when these steps are performed in this order, a single crystal having a higher coercive field value than the first single crystal is produced.
2. The method for producing a perovskite single crystal according to claim 1, wherein the acceptor is Mn.
3. The method for producing a perovskite single crystal according to claim 1, wherein the firing temperature under a reducing atmosphere in step (2) is equal to or lower than the firing temperature at which the first single crystal is produced in step (1).
4. The method for producing a perovskite single crystal according to claim 1, wherein the firing temperature under an atmospheric atmosphere in step (3) is equal to or lower than the firing temperature under a reducing atmosphere in step (2).
5. The method for producing a perovskite single crystal according to claim 1, wherein the raw material contains Ba, Ti, and Zr.
6. The method for producing a perovskite single crystal according to claim 1, wherein the production of the first single crystal in step (1) is by a solid phase growth method.
7. The method for producing a perovskite single crystal according to claim 1, wherein the raw material includes an oxide containing Ba, Ti, and Zr, wherein x as a molar ratio of Zr to the total of Ti and Zr satisfies 0.02 ≤ x ≤ 0.13, and the Mn content is 0.04 mass parts or more and 0.36 mass parts or less with respect to 100 mass parts of the oxide in terms of metal.
8. The method for producing a perovskite single crystal according to claim 1, wherein the raw material includes an oxide containing Ba, Ti, and Zr, Mn, Bi, and Li, wherein x as a molar ratio of Zr to the total of Ti and Zr satisfies 0.02 ≤ x ≤ 0.13, the Mn content is 0.04 mass parts or more and 0.36 mass parts or less with respect to 100 mass parts of the oxide in terms of metal, the Bi content is more than 0 mass parts and 0.20 mass parts or less with respect to 100 mass parts of the oxide in terms of metal, and the Li content is 0.05 mass parts or more and 0.20 mass parts or less with respect to 100 mass parts of the oxide in terms of metal.
10. The method for producing a perovskite single crystal according to claim 1, wherein the firing temperature under a reducing atmosphere in step (2) is 1280°C or higher.
11. The method for producing a perovskite single crystal according to claim 1, wherein the firing temperature under an atmospheric atmosphere in step (3) is 1000°C or lower.
12. A perovskite single crystal, comprising an oxide containing Ba, Ti, and Zr, wherein x as a molar ratio of Zr to the total of Ti and Zr satisfies 0.02 ≤ x ≤ 0.13, and Mn, wherein the Mn content of the single crystal is 0.04 mass parts or more and 0.36 mass parts or less with respect to 100 mass parts of the oxide in terms of metal. 9. The method for producing a perovskite single crystal according to claim 1, wherein the reducing atmosphere in step (2) is a gas containing argon and hydrogen, and has an oxygen partial pressure P(02) of 1 x 10 -10 Pa or lower. The single crystal optionally contains Bi, and the Bi content is 0 mass part or more and 0.20 mass part or less with respect to 100 mass parts of the oxide in terms of metal, and The single crystal has an electromechanical coupling coefficient k of 80% or more at 25°C 33 80% or more and a coercive field of 2.5 kV / cm or more.
13. The perovskite single crystal according to claim 12, wherein the single crystal contains less than 1000 ppm of a Pb component.
14. The perovskite single crystal according to claim 12, wherein the piezoelectric constant d 33 of the single crystal has a variation amplitude (%) of 65% or less, which is represented by the following expression (1): d = d0 + Δd (1) where d0 is a piezoelectric constant of the single crystal at 20°C, Δd is a variation amplitude of the piezoelectric constant d at 20°C, and d is a piezoelectric constant of the single crystal at 80°C. 100 x Ad 33@0℃至70℃ / d 33@0℃ (1).
15. The perovskite single crystal according to claim 12, wherein the single crystal has a maximum value of relative dielectric constant εr in a range of above 0°C and below 70°C of 6500 or less. 33 15. The perovskite single crystal according to claim 12, wherein the single crystal has a maximum value of relative dielectric constant εr in a range of above 0°C and below 70°C of 6500 or less.
16. The perovskite single crystal according to claim 12, wherein the single crystal has a maximum value of relative dielectric constant ε 33 of 4200 or less in a range of 0°C or more and 60°C or less.
17. A piezoelectric element including a plurality of electrodes and a single crystal, wherein the single crystal is the single crystal according to any one of claims 12 to 16.
18. An ultrasonic motor comprising at least: A vibration body provided with the piezoelectric element according to claim 17; and a moving body in contact with the vibration body.
19. An optical device including the ultrasonic motor according to claim 18 in a driving section.
20. A vibration device including a vibration body having a vibration plate provided with the piezoelectric element according to claim 17.
21. A dust removing device including the vibration device according to claim 20 in a vibration section.
22. An image pickup device including at least the dust removing device according to claim 21 and an image pickup element unit, wherein the vibration plate of the dust removing device is disposed on the light-receiving surface side of the image pickup element unit.
23. An ultrasonic probe including the piezoelectric element according to claim 17, wherein the ultrasonic probe transmits and receives ultrasonic waves through the piezoelectric element.
24. An ultrasonic diagnostic device including at least the ultrasonic probe according to claim 23 and an image output section.
25. An ultrasonic diagnostic system comprising: The ultrasonic probe according to claim 23; a transmission section that transmits a signal output from the ultrasonic probe; and a reception section that receives a signal transmitted from the transmission section.
26. An electronic device provided with a piezoelectric acoustic member including the piezoelectric element according to claim 17.